Adhesive film for metal terminal, method for manufacturing same, and metal terminal
The adhesive film with a specific sea-island structure in a laminated polyolefin layer configuration addresses adhesion issues in power storage devices, maintaining strong bonding to metal terminals and resisting electrolyte exposure.
Patent Information
- Application Number
- CN202411246291.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-08
- Filing Date
- 2020-11-09
- Publication Date
- 2024-12-13
AI Technical Summary
Existing adhesive films for metal terminals in power storage devices do not adequately maintain adhesion to metal terminals after heat sealing and are susceptible to adhesion loss when exposed to electrolytes.
An adhesive film composed of a laminated body with a first polyolefin layer on the metal terminal side and a second polyolefin layer on the outer packaging material side, featuring a sea-island structure with a specific ratio of island portions in the cross-sectional image, which enhances adhesion and resists adhesion loss when exposed to electrolytes.
The adhesive film maintains excellent adhesion to metal terminals during heat sealing and effectively prevents adhesion loss even when contacted by electrolytes, ensuring reliable electrical connections.
Smart Images

Figure CN119119884A_ABST
Abstract
Description
[0001] This application is a divisional application of the patent application with application number 202080077221.2 filed on November 9, 2020. Technical Field
[0002] The present invention relates to an adhesive film for metal terminals, a method for producing the adhesive film for metal terminals, a metal terminal with the adhesive film for metal terminals, a power storage device using the adhesive film for metal terminals, and a method for producing the power storage device. Background Art
[0003] Various types of power storage devices have been developed. However, in all power storage devices, outer packaging materials for power storage devices are indispensable components for encapsulating power storage device components such as electrodes and electrolytes. In the past, outer packaging materials for power storage devices made of metal were mostly used. However, in recent years, with the high performance of electric vehicles, hybrid electric vehicles, computers, cameras, mobile phones, etc., power storage devices require various shapes, and also require thinning and light weight. However, the outer packaging materials for power storage devices made of metal that are currently mostly used have the disadvantages of being difficult to cope with the diversity of shapes and also having a limit to light weight.
[0004] Therefore, in recent years, as an outer packaging material for storage devices that can be easily processed into various shapes and can achieve thinning and lightening, a laminated sheet having a base layer / adhesive layer / barrier layer / thermo-fusible resin layer laminated in this order has been proposed. When such a film-shaped outer packaging material for storage devices is used, the outer packaging material for storage devices is heat-fused by heat sealing while the innermost heat-fusible resin layers of the outer packaging material for storage devices are facing each other, thereby encapsulating the storage device element with the outer packaging material for storage devices.
[0005] The metal terminal extends from the heat-sealed portion of the outer packaging material for the storage device, and the storage device element encapsulated by the storage device outer packaging material is electrically connected to the outside through the metal terminal electrically connected to the electrode of the storage device element. That is, in the heat-sealed portion of the outer packaging material for the storage device, the portion where the metal terminal exists is heat-sealed in a state where the metal terminal is sandwiched by the heat-fusible resin layer. The metal terminal and the heat-fusible resin layer are composed of different types of materials, so the adhesion is easily reduced at the interface between the metal terminal and the heat-fusible resin layer.
[0006] Therefore, an adhesive film may be disposed between the metal terminal and the heat-adhesive resin layer for the purpose of improving the adhesion between them. As such an adhesive film, for example, an adhesive film described in Patent Document 1 can be cited.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2015-79638 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] Such an adhesive film is required to have excellent adhesion to a metal terminal after heat sealing.
[0012] Furthermore, the adhesive film is required to appropriately suppress a decrease in adhesion with a metal terminal even when the electrolyte solution enclosed by the packaging material comes into contact with the adhesive film.
[0013] However, the current adhesive films do not fully consider the adhesion with the metal terminals after contacting the electrolyte. In addition to pursuing the excellent adhesion between the adhesive film and the metal terminal obtained by heat sealing, the inventors of the present invention also pursue the ability to suppress the decrease in adhesion with the metal terminal when the electrolyte adheres to the adhesive film that is tightly bonded to the metal terminal.
[0014] The main object of the present invention is to provide an adhesive film for metal terminals which has excellent adhesion to metal terminals obtained by heat sealing and can appropriately suppress the decrease in adhesion to the metal terminals even when an electrolyte adheres to the adhesive film in close contact with the metal terminals. The present invention also aims to provide a method for manufacturing the adhesive film for metal terminals, a metal terminal with the adhesive film for metal terminals using the adhesive film for metal terminals, a storage device using the adhesive film for metal terminals, and a method for manufacturing the storage device.
[0015] Technical solutions for solving technical problems
[0016] The inventors of the present invention have conducted in-depth research to solve the above technical problems. As a result, it was found that an adhesive film for metal terminals composed of a laminated body, the laminated body sequentially having a first polyolefin layer arranged on the metal terminal side, a substrate, and a second polyolefin layer arranged on the outer packaging material side of the storage device, by making the ratio of the total area of the island part of the sea-island structure within a specified range in the cross-sectional image of the surface part of the metal terminal side of the first polyolefin layer after the adhesive film for metal terminals is left to stand for 12 seconds in a heating and pressurizing environment at a temperature of 190°C and a surface pressure of 0.016MPa, and then left to stand for 1 hour in an environment at a temperature of 25°C (which is a general heating condition during heat sealing), the adhesive film obtained by heat sealing has excellent adhesion to the metal terminal, and even when the electrolyte is attached to the adhesive film that is closely attached to the metal terminal by heat sealing, the decrease in adhesion to the metal terminal can be appropriately suppressed. The present invention was completed by further repeated research based on the above insights.
[0017] That is, the present invention provides the inventions of the following aspects.
[0018] An adhesive film for metal terminals, which is present between a metal terminal electrically connected to an electrode of an electric storage device element and an outer packaging material for an electric storage device that seals the electric storage device element.
[0019] The adhesive film for metal terminals is composed of a laminated body, which has a first polyolefin layer arranged on the metal terminal side, a substrate, and a second polyolefin layer arranged on the outer packaging material side of the power storage device in this order.
[0020] In a cross-sectional image obtained using a field emission scanning electron microscope of a cross section of the first polyolefin layer in a direction parallel to TD (Transverse Direction) and in the thickness direction, a sea-island structure was observed.
[0021] The cross-sectional image is a cross-sectional image obtained from the surface on the opposite side of the surface on the substrate side to a portion having a thickness of 30% when the thickness of the first polyolefin layer is taken as 100%.
[0022] In the cross-sectional image after the adhesive film for metal terminals is allowed to stand for 12 seconds in a heating and pressurizing environment at a temperature of 190° C. and a surface pressure of 0.016 MPa and then for 1 hour in an environment at a temperature of 25° C., the ratio of the total area of the island portions of the sea-island structure is 25.0% to 35.0%.
[0023] Effects of the Invention
[0024] According to the present invention, an adhesive film for metal terminals is provided, wherein the adhesive film obtained by heat sealing has excellent adhesion to the metal terminal, and even when an electrolyte adheres to the adhesive film that is closely attached to the metal terminal by heat sealing, the decrease in adhesion to the metal terminal can be appropriately suppressed. The present invention also aims to provide a method for manufacturing the adhesive film for metal terminals, a metal terminal with the adhesive film for metal terminals using the adhesive film for metal terminals, a storage device using the adhesive film for metal terminals, and a method for manufacturing the storage device. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic top view of the power storage device of the present invention.
[0026] Figure 2 yes Figure 1 Schematic diagram of the cross section along line A-A′.
[0027] Figure 3 yes Figure 1 Schematic diagram of the cross section along line BB′.
[0028] Figure 4 It is a schematic cross-sectional view of the adhesive film for metal terminals of the present invention.
[0029] Figure 5 It is a schematic cross-sectional view of the adhesive film for metal terminals of the present invention.
[0030] Figure 6 It is a schematic cross-sectional view of the outer packaging material for an electric storage device of the present invention.
[0031] Figure 7 In the examples, the diagram is a schematic cross-sectional view of a laminate of adhesive film / metal terminal / adhesive film (metal terminal with adhesive film for metal terminal) obtained by sandwiching a metal terminal between two adhesive films and thermally fusing them.
[0032] Figure 8 This is a cross-sectional image (binarized using image processing software) obtained using a field emission scanning electron microscope for a cross section (surface portion on the metal terminal side (opposite side of the substrate)) of the first polyolefin layer of the adhesive film for metal terminals obtained in Example 1 in a direction parallel to TD and in the thickness direction. This is a cross-sectional image obtained from the surface of the first polyolefin layer from the surface on the opposite side of the substrate side to the portion of 30% thickness. The cross-sectional image on the left is an image before the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, and the cross-sectional image on the right is an image after the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds.
[0033] Fig. 9 This is a cross-sectional image (binarized using image processing software) obtained using a field emission scanning electron microscope for a cross section parallel to TD and in the thickness direction (surface portion on the substrate side) of the first polyolefin layer of the adhesive film for metal terminals obtained in Example 1. This is a cross-sectional image obtained from the surface of the substrate side to the portion of 30% thickness of the first polyolefin layer. The cross-sectional image on the left is an image before the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, and the cross-sectional image on the right is an image after the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds.
[0034] Fig.10This is a cross-sectional image (binarized using image processing software) obtained using a field emission scanning electron microscope for a cross section (surface portion on the metal terminal side (opposite side of the substrate)) of the first polyolefin layer of the adhesive film for metal terminals obtained in Comparative Example 1 in a direction parallel to TD and in the thickness direction. This is a cross-sectional image obtained from the surface of the first polyolefin layer from the surface on the opposite side of the substrate side to the portion of 30% thickness. The cross-sectional image on the left is an image before the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, and the cross-sectional image on the right is an image after the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds.
[0035] Fig.11 This is a cross-sectional image (binarized using image processing software) obtained using a field emission scanning electron microscope for a cross section parallel to TD and in the thickness direction (surface portion on the substrate side) of the first polyolefin layer of the adhesive film for metal terminals obtained in Comparative Example 1. This is a cross-sectional image obtained from the surface of the substrate side to the portion of 30% thickness of the first polyolefin layer. The cross-sectional image on the left is an image before the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, and the cross-sectional image on the right is an image after the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds.
[0036] Fig.12 This is a cross-sectional image (binarized using image processing software) obtained using a field emission scanning electron microscope for a cross section in the direction parallel to TD and in the thickness direction (surface portion on the metal terminal side (opposite side of the substrate)) of the first polyolefin layer of the adhesive film for metal terminals obtained in Comparative Example 2. This is a cross-sectional image obtained from the surface of the first polyolefin layer on the opposite side of the substrate side to the portion of 30% thickness. The cross-sectional image on the left is an image before the first polyolefin layer is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, and the cross-sectional image on the right is an image after the first polyolefin layer is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds.
[0037] Fig.13This is a cross-sectional image (binarized using image processing software) obtained using a field emission scanning electron microscope for a cross section parallel to TD and in the thickness direction (surface portion on the substrate side) of the first polyolefin layer of the adhesive film for metal terminals obtained in Comparative Example 2. This is a cross-sectional image obtained within the range from the substrate side surface to the 30% thickness portion of the first polyolefin layer. The cross-sectional image on the left is an image before the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, and the cross-sectional image on the right is an image after the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds.
[0038] Fig.14 It is a schematic diagram showing MD, TD, and thickness direction (y) of a production line of an adhesive film for a metal terminal. DETAILED DESCRIPTION
[0039] The adhesive film for metal terminals of the present invention is present between a metal terminal electrically connected to an electrode of an electric storage device element and an outer packaging material for an electric storage device that encapsulates the electric storage device element. The adhesive film for metal terminals is characterized in that the adhesive film for metal terminals is composed of a laminate, the laminate having, in sequence, a first polyolefin layer arranged on the metal terminal side, a substrate, and a second polyolefin layer arranged on the outer packaging material side of the electric storage device, and an island structure is observed in a cross-sectional image obtained using a field emission scanning electron microscope for a cross section in a direction parallel to TD and in a thickness direction of the first polyolefin layer, the cross-sectional image being a cross-sectional image obtained in a range from a surface on the side opposite to the surface on the substrate side to a portion with a thickness of 30% when the thickness of the first polyolefin layer is taken as 100%, and in the cross-sectional image after the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the ratio of the total area of the island portions of the island structure is 25.0% or more and 35.0% or less.
[0040] In the adhesive film for metal terminals of the present invention, in the cross-sectional image after the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016 MPa for 12 seconds, the ratio of the total area of the island portions of the sea-island structure is set to be greater than 25.0% and less than 35.0%. Therefore, the adhesive film obtained by heat sealing has excellent adhesion to the metal terminal, and even in the case where the electrolyte adheres to the adhesive film that is tightly bonded to the metal terminal by heat sealing, the decrease in adhesion to the metal terminal can be appropriately suppressed. The above-mentioned cross-sectional image is a cross-sectional image of the surface portion of the first polyolefin layer arranged on the metal terminal side (specifically, a cross-sectional image obtained in the range from the surface on the opposite side to the surface on the substrate side to a portion with a thickness of 30% when the thickness of the first polyolefin layer is taken as 100%).
[0041] In addition, the electric storage device of the present invention includes: an electric storage device element having at least a positive electrode, a negative electrode and an electrolyte; an outer packaging material for an electric storage device that encapsulates the electric storage device element; and metal terminals that are electrically connected to the positive electrode and the negative electrode, respectively, and extend to the outside of the outer packaging material for the electric storage device, and the electric storage device is characterized in that the adhesive film for metal terminals of the present invention is present between the metal terminals and the outer packaging material for the electric storage device. The adhesive film for metal terminals of the present invention and a method for manufacturing the same, and an electric storage device using the adhesive film for metal terminals and a method for manufacturing the same are described in detail below.
[0042] In the present specification, regarding numerical ranges, the numerical range indicated by "to" means "above" or "below." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.
[0043] In addition, as a method for confirming the MD of the adhesive film for metal terminals, there is a method of observing the cross section of the adhesive film for metal terminals (e.g., the cross section of the first polyolefin layer, the substrate, or the second polyolefin layer) using an electron microscope and confirming the sea island structure. In this method, the direction parallel to the cross section with the largest diameter average value of the island shape in the direction perpendicular to the thickness direction of the adhesive film for metal terminals is judged as MD. Specifically, for the cross section in the length direction of the adhesive film for metal terminals, and each cross section (a total of 10 cross sections) that changes the angle every 10 degrees from the direction parallel to the cross section in the length direction until the direction perpendicular to the cross section in the length direction, respectively, is observed using an electron microscope photograph to confirm the sea island structure. Then, for each cross section, the shape of each island is observed separately. For the shape of each island, the straight line distance connecting the leftmost end in the direction perpendicular to the thickness direction of the adhesive film for metal terminals and the rightmost end in the vertical direction is taken as the diameter y. In each cross section, the average value of the diameter y of the island shape is calculated according to the order of the first 20 diameters y from large to small. The direction parallel to the cross section where the average value of the diameter y of the island shape is the largest is determined as MD.
[0044] 1. Adhesive film for metal terminals
[0045] The adhesive film for metal terminals of the present invention is present between the metal terminal electrically connected to the electrode of the storage device element and the outer packaging material for the storage device that encapsulates the storage device element. Figures 1 to 3As shown in the figure, the adhesive film 1 for metal terminal of the present invention exists between the metal terminal 2 electrically connected to the electrode of the storage device element 4 and the outer packaging material 3 for the storage device that encapsulates the storage device element 4. In addition, the metal terminal 2 protrudes outside the outer packaging material 3 for the storage device, and is sandwiched by the outer packaging material 3 for the storage device through the adhesive film 1 for metal terminal at the peripheral edge 3a of the heat-sealed outer packaging material 3 for the storage device. In the present invention, the heating temperature when heat-sealing the outer packaging material for the storage device is generally in the range of about 160 to 190°C, and the pressure is generally in the range of about 1.0 to 2.0 MPa. In addition, in the process of bonding the metal terminal and the outer packaging material for the storage device through the adhesive film, multiple heating and pressurization are generally performed, such as the preliminary bonding process and the main bonding process with the metal terminal. The preliminary bonding process is a process of temporarily fixing the metal terminal and the adhesive film and removing bubbles, and the formal bonding process is a process of heating and pressurizing the adhesive film and the metal terminal one or more times at a higher temperature than the preliminary bonding process to bond the adhesive film to the metal terminal. The preliminary bonding process of the adhesive film for the metal terminal and the metal terminal is performed, for example, at a temperature of about 140 to 160°C, a pressure of about 0.01 to 1.0 MPa, a time of about 3 to 15 seconds, and a number of about 3 to 6 times; the formal bonding process is performed, for example, at a temperature of about 160 to 240°C, a pressure of about 0.01 to 1.0 MPa, a time of about 3 to 15 seconds, and a number of about 1 to 3 times.
[0046] The adhesive film 1 for metal terminals of the present invention is provided to improve the closeness between the metal terminal 2 and the outer packaging material 3 for the storage device. By improving the closeness between the metal terminal 2 and the outer packaging material 3 for the storage device, the sealing of the storage device element 4 is improved. As described above, when the storage device element 4 is heat-sealed, the storage device element is packaged in a manner that the metal terminal 2 electrically connected to the electrode of the storage device element 4 extends to the outside of the outer packaging material 3 for the storage device. At this time, the metal terminal 2 formed of metal and the heat-fusible resin layer 35 (a layer formed of a heat-fusible resin such as polyolefin) located in the innermost layer of the outer packaging material 3 for the storage device are formed of different types of materials. Therefore, when such an adhesive film is not used, the sealing of the storage device element is easily reduced at the interface between the metal terminal 2 and the heat-fusible resin layer 35.
[0047] The adhesive film 1 for metal terminal of the present invention is as follows Figure 4 and Figure 5The structure shown includes at least a first polyolefin layer 12a, a substrate 11, and a second polyolefin layer 12b laminated in sequence. The first polyolefin layer 12a is arranged on the metal terminal 2 side. In addition, the second polyolefin layer 12b is arranged on the outer packaging material 3 side for the storage device. In the adhesive film 1 for metal terminals of the present invention, the first polyolefin layer 12a and the second polyolefin layer 12b are respectively located on the surfaces of both sides.
[0048] In the adhesive film 1 for metal terminals of the present invention, the first polyolefin layer 12a and the second polyolefin layer 12b are layers containing polyolefin resins, respectively. As polyolefin resins, polyolefins, acid-modified polyolefins, etc. can be cited. The first polyolefin layer 12a preferably contains acid-modified polyolefins in the polyolefin resin, and more preferably a layer formed by acid-modified polyolefins. In addition, the second polyolefin layer 12b preferably contains polyolefins or acid-modified polyolefins in the polyolefin resin, more preferably contains polyolefins, and further preferably a layer formed by polyolefins. By making the resin forming the second polyolefin layer 12b disposed on the side of the outer packaging material 3 for the storage device and the resin forming the heat-melting resin layer 35 of the outer packaging material 3 for the storage device the same resin, the adhesion between the adhesive film 1 for metal terminals of the present invention and the outer packaging material for the storage device is improved.
[0049] Furthermore, the substrate 11 preferably includes a polyolefin-based resin, more preferably includes polyolefin, and more preferably is a layer formed of polyolefin.
[0050] In the first polyolefin layer 12a, the second polyolefin layer 12b and the substrate 11, the polyolefin resin is preferably a polypropylene resin, the polyolefin is preferably polypropylene, and the acid-modified polyolefin is preferably acid-modified polypropylene. In addition, the polyolefin resins such as polyolefin and acid-modified polyolefin may contain known additives and fillers and pigments described later.
[0051] Specific examples of preferred laminated structures of the adhesive film 1 for metal terminals of the present invention include: a three-layer structure in which a first polyolefin layer formed by acid-modified polypropylene / a substrate formed by polypropylene / a second polyolefin layer formed by polypropylene are laminated in sequence; a three-layer structure in which a first polyolefin layer formed by acid-modified polypropylene / a substrate formed by polypropylene / a second polyolefin layer formed by acid-modified polypropylene are laminated in sequence, etc. Among these, a three-layer structure in which a first polyolefin layer formed by acid-modified polypropylene / a substrate formed by polypropylene / a second polyolefin layer formed by polypropylene are laminated in sequence is particularly preferred.
[0052] The details of the materials constituting the first polyolefin layer 12 a , the second polyolefin layer 12 b , and the substrate 11 will be described later.
[0053] When the adhesive film 1 for metal terminals of the present invention is arranged between the metal terminal 2 of the power storage device 10 and the outer packaging material 3 for the power storage device, the surface of the metal terminal 2 composed of metal and the heat-fusible resin layer 35 (a layer formed of a heat-fusible resin such as polyolefin) of the outer packaging material 3 for the power storage device are bonded via the adhesive film 1 for metal terminals. The first polyolefin layer 12a of the adhesive film 1 for metal terminals is arranged on the metal terminal 2 side, and the second polyolefin layer 12b is arranged on the outer packaging material 3 side for the power storage device, the first polyolefin layer 12a is in close contact with the metal terminal 2, and the second polyolefin layer 12b is in close contact with the heat-fusible resin layer 35 of the outer packaging material 3 for the power storage device.
[0054] In the adhesive film 1 for metal terminals of the present invention, a sea-island structure is observed in a cross-sectional image obtained by using a field emission scanning electron microscope for a cross section of the first polyolefin layer 12a in a direction parallel to TD and in a thickness direction, and the cross-sectional image is a cross-sectional image obtained from the surface on the opposite side of the surface on the substrate 11 side to a portion of 30% thickness when the thickness of the first polyolefin layer 12a is 100%. In addition, in the cross-sectional image obtained after heating the adhesive film for metal terminals at a temperature of 190°C and a surface pressure of 0.016 MPa for 12 seconds, the ratio of the total area of the island portions of the sea-island structure is 25.0 to 35.0%. In particular, the method of heating the adhesive film for metal terminals at a temperature of 190°C and a surface pressure of 0.016 MPa for 12 seconds is the same as the measurement of the adhesion strength in the examples described later, and a method of heating for 12 seconds using a hot plate heated to 190°C is adopted.
[0055] In addition, when the thickness of the first polyolefin layer 12a is taken as 100%, the range from the surface on the opposite side to the surface on the substrate 11 side to the portion of 30% thickness is sometimes simply referred to as the surface portion on the opposite side to the surface on the substrate 11 side of the first polyolefin layer 12a (or the surface portion on the metal terminal 2 side of the first polyolefin layer 12a), etc. Similarly, when the thickness of the first polyolefin layer 12a is taken as 100%, the range from the surface on the substrate 11 side to the portion of 30% thickness is sometimes simply referred to as the surface portion on the substrate 11 side of the first polyolefin layer 12a, etc.
[0056] The ratio of the total area of the island portions of the sea-island structure can be in the range of 25.0 to 35.0%, but from the perspective that the adhesion between the adhesive film obtained by heat sealing and the metal terminal is particularly excellent, and when the electrolyte is attached to the adhesive film that is closely attached to the metal terminal by heat sealing, the decrease in the adhesion with the metal terminal can be more appropriately suppressed, the ratio of the total area of the island portions of the sea-island structure is preferably about 26.0% or more, and more preferably about 28.0% or more. In addition, the ratio of the total area of the island portions of the sea-island structure is preferably about 32.0% or less, and more preferably about 30.0% or less. The preferred range of the ratio of the total area of the island portions of the sea-island structure is about 26.0 to 32.0%, about 26.0 to 30.0%, about 28.0 to 35.0%, about 28.0 to 32.0%, and about 28.0 to 30.0%.
[0057] The observation of the sea-island structure in the cross-sectional image of the first polyolefin layer was performed as follows.
[0058] <Observation of sea-island structure in cross-sectional images>
[0059] The metal terminal is embedded in a thermosetting epoxy resin with an adhesive film and cured. A commercially available rotary ultrathin slicer (e.g., UC6 manufactured by LEICA) and a diamond knife are used to make a cross section in the target direction (a cross section along the TD). At this time, the cross section is made at -70°C using a cryo-microtomy method using liquid nitrogen. Together with the embedding resin, it is stained with ruthenium tetroxide overnight. After staining, since polypropylene expands, the expanded part is trimmed using an ultrathin slicer, and 100nm to 300nm is cut off each time in the MD direction, with a total of about 1μm to 2μm cut off, and the exposed cross section is observed as described below. For the stained cross section, a field emission scanning electron microscope (e.g., S-4800TYPE1 manufactured by Hitachi High-Technologies Corporation, measurement conditions: 3kV 20mA High WD6mm detector (Upper)) is used to observe and obtain an image (magnification is 10,000 times). In addition, for the surface portion of the first polyolefin layer on the metal terminal side (when the thickness of the first polyolefin layer is 100%, the range from the surface on the opposite side of the substrate side to the portion of 30% thickness, refer to Figure 4) to obtain a cross-sectional image. In addition, by changing the observation position, a cross-sectional image is also obtained for the surface portion of the substrate side of the first polyolefin layer (when the thickness of the first polyolefin layer is taken as 100%, the range from the surface of the substrate side to the portion with 30% thickness). Next, using image processing software that can binarize the image (for example, image analysis software WinROOF (Ver7.4) manufactured by Mitani Shoji, the island portion and the sea portion of the sea-island structure are binarized in this image to obtain the number of island portions, the ratio of the total area of the island portions (total area of the island portions / area of the measurement range of the image), the average particle size of the island portions, the particle size deviation σ of the island portions, and the roundness of the island portions.
[0060] The binarized cross-sectional images of Example 1 and Comparative Examples 1 and 2 are shown in FIG. Figure 8 to Figure 13 . Figure 8 is the surface portion of the first polyolefin layer on the metal terminal side of Example 1, Fig. 9 is the surface portion of the first polyolefin layer on the substrate side of Example 1, Fig.10 is the surface portion of the first polyolefin layer on the metal terminal side of Comparative Example 1, Fig.11 is the surface portion of the substrate side of the first polyolefin layer of Comparative Example 1, Fig.12 is the surface portion of the first polyolefin layer on the metal terminal side of Comparative Example 2, Fig.13 is the surface portion of the substrate side of the first polyolefin layer of Comparative Example 2. Figure 8 to Figure 13 In each figure, the image on the left is an image before the adhesive film for metal terminal is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, and the image on the right is an image after the adhesive film for metal terminal is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds (similar to the measurement of the adhesion strength described later, the adhesive film for metal terminal is heated at a surface pressure of 0.016MPa for 12 seconds using a hot plate heated to 190°C (heated in a manner such that the first polyolefin layer side is the hot plate side)). In addition, in this measurement, since the island part is further dyed than the sea part, the island part appears brighter than the sea part.
[0061] [Image processing conditions]
[0062] Image processing can be performed using the image analysis software ImageJ. Specifically, the SEM image is obtained in the form of a digital file of a grayscale image (JPEG format, etc.), and is processed according to the following binarization processing steps and parameters, and the grayscale (bright) pixels above the threshold are output as 1, and the grayscale (dark) pixels below the threshold are output as 0, which are respectively defined as the island part and the sea part.
[0063] <Binarization>
[0064] 1. Despeckle
[0065] 2. Remove the outline of the island (Remove Outliers radius = 4threshold = 1which = Bright)
[0066] 3. Remove the outline of the sea (Remove Outliers radius = 4threshold = 1which = Dark)
[0067] 4. Despeckle
[0068] 5. Gaussian blur in the X-axis (short side of the sample) direction (threshold = 3 pixels)
[0069] 6. Contrast enhancement (saturated = 0.2)
[0070] 7. Remove the outline of the island (Remove Outliers radius = 4threshold = 1which = Bright)
[0071] 8. Remove the outline of the sea (Remove Outliers radius = 4threshold = 1which = Dark)
[0072] 9. Otsu binarization
[0073] The average particle size of the island portion is a value calculated based on the maximum Feret diameter of the island portion of the image binarized by the image analysis software ImageJ. In addition, the particle size deviation σ of the island portion is a value calculated based on the standard deviation of the average particle size. In addition, the roundness of the island portion is a value calculated by the difference between the radii of the two concentric circles when the interval between the concentric circles becomes the smallest when the island portion of the image binarized by the image analysis software ImageJ is sandwiched between two concentric geometric circles.
[0074] For example Figure 4 As shown in the schematic diagram of FIG. 1 , the cross-sectional image is a cross-sectional image obtained by taking the total thickness of the first polyolefin layer 12a as 100% and the cross-sectional image is obtained by taking the cross-sectional image from the surface on the metal terminal side (opposite to the substrate 11) to the portion with a thickness of 30% ( Figure 4The cross-hatched area). The surface of the first polyolefin layer 12a on the opposite side to the substrate 11 has a thickness of 0%. To illustrate with a specific example, in the case of an adhesive film for a metal terminal formed by laminating a first polyolefin layer (thickness 50 μm) / substrate (thickness 50 μm) / second polyolefin layer (thickness 50 μm) in sequence as in Example 1 described later, the thickness of the first polyolefin layer of 50 μm is taken as 100%. In addition, the thickness of the first polyolefin layer 12a at the position on the opposite side to the substrate 11 is taken as 0%. Then, a cross-sectional image is obtained using a field emission scanning electron microscope in the range from the surface (thickness 0%) to the position of 30% thickness (that is, 50 μm is taken as 100%, and the position of 30% thickness is the position of 15 μm thickness from the surface of the first polyolefin layer on the opposite side to the substrate layer side to the substrate side).
[0075] In addition, the observation of the sea-island structure in the cross-sectional image means that the sea portion (sea portion) and the island portion (island portion) are observed in the cross-sectional image. For example, when a small amount of polyethylene is added to acid-modified polypropylene as the resin composition forming the first polyolefin layer 12a, and the first polyolefin layer 12a is formed by melt extrusion molding, a sea-island structure is formed in which the island portions of polyethylene are dispersed in the sea portion of the acid-modified polypropylene. In addition, in order to observe the sea-island structure, as described above, the cross section of the first polyolefin layer 12a is stained with ruthenium tetroxide or the like, and a cross-sectional image is obtained and observed using a field emission scanning electron microscope.
[0076] In the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion on the metal terminal side (specifically, the portion from the surface on the metal terminal side (the side opposite to the substrate 11) to 30% thickness) after the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, the total area of the island portions of the sea-island structure accounts for 25.0 to 35.0%. Since the adhesive film 1 for metal terminals of the present invention has such a feature, the adhesive film obtained by heat sealing has excellent adhesion to the metal terminal, and even when an electrolyte is attached to the adhesive film that is tightly bonded to the metal terminal by heat sealing, the decrease in adhesion to the metal terminal can be appropriately suppressed. More specifically, in the first polyolefin layer 12a arranged on the metal terminal side of the adhesive film 1 for metal terminals of the present invention, by setting the total area of the island portion of the sea-island structure of the surface portion on the metal terminal 2 side (the island portion, for example, is mainly formed of polyethylene which makes the first polyolefin layer 12a soft and improves the adhesion but has slightly poor electrolyte resistance) within an appropriate range of 25.0 to 35.0%, it is possible to ensure excellent adhesion with the metal terminal and to appropriately suppress the penetration of the electrolyte. As a result, it can be considered that the decrease in adhesion with the metal terminal when the electrolyte is attached can be suppressed. The surface portion on the metal terminal side after the adhesive film for metal terminal is heated at a temperature of 190°C and a surface pressure of 0.016 MPa for 12 seconds is equivalent to the surface portion after the first polyolefin layer 12a is tightly bonded to the metal terminal 2 by heat sealing. It can be said that in the adhesive film 1 for metal terminal of the present invention, the ratio of the total area of the island portion of the sea-island structure of the surface portion on the metal terminal 2 side after the heat sealing of the first polyolefin layer 12a is set within an appropriate range of 25.0 to 35.0%.
[0077] In addition, in the adhesive film 1 for metal terminals of the present invention, the sea island structure is also generally observed in the cross-sectional image after the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, and the cross-sectional image is a cross-sectional image obtained within the range of the surface portion on the substrate 11 side (specifically, from the surface of the substrate 11 side to the portion of 30% thickness) when the thickness of the first polyolefin layer 12a is taken as 100%. The ratio of the total area of the island portion of the sea island structure in the cross-sectional image of the surface portion on the substrate 11 side is not particularly limited, and is preferably about 25.0% or more, and more preferably about 30.0% or more. In addition, as the ratio of the total area of the island portion, it is preferably about 35.0% or less, and more preferably about 33.0% or less. As the preferred range of the ratio of the total area of the island portion, it is about 25.0 to 35.0%, about 25.0 to 33.0%, about 30.0 to 35.0%, and about 30.0 to 33.0%. Here, the method of heating the adhesive film for metal terminal at 190° C. and a surface pressure of 0.016 MPa for 12 seconds was as described above, and the method of heating on a hot plate heated to 190° C. for 12 seconds was adopted in the same manner as the measurement of adhesion strength in Examples described below.
[0078] In the adhesive film 1 for metal terminals of the present invention, for example, the ratio of the total area of the island portions of the sea-island structure in the above-mentioned cross-sectional image of the surface portion on the metal terminal 2 side after the adhesive film 1 for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds may be smaller or larger than the ratio of the total area of the island portions of the sea-island structure in the above-mentioned cross-sectional image of the surface portion on the substrate 11 side, but preferably the same degree. That is, in the adhesive film 1 for metal terminals of the present invention, the ratio of the total area of the island portions on the surface portion on the metal terminal 2 side may be smaller or larger than the surface portion on the substrate 11 side, but preferably the same degree. In addition, it is preferred that the ratio of the total area of the island portions of the sea-island structure in the above-mentioned cross-sectional image of the surface portion on the metal terminal 2 side is the same degree before and after the adhesive film 1 for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, and it is preferred that the ratio of the total area of the island portions of the sea-island structure in the above-mentioned cross-sectional image of the surface portion on the substrate 11 side is the same degree.
[0079] In addition, in the adhesive film 1 for metal terminals of the present invention, an island structure is also generally observed in a cross-sectional image before the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, and the cross-sectional image is a cross-sectional image obtained within the range of the surface portion on the metal terminal 2 side (specifically, from the surface on the opposite side of the substrate 11 to the portion of 30% thickness) when the thickness of the first polyolefin layer 12a is taken as 100%. The ratio of the total area of the island portion of the island structure in the cross-sectional image of the surface portion on the metal terminal 2 side of the first polyolefin layer 12a before heating is not particularly limited, and is preferably about 22.0% or more, and more preferably about 24.0% or more. In addition, as the ratio of the total area of the island portion, it is preferably about 32.0% or less, and more preferably about 28.0% or less. Preferred ranges of the ratio of the total area of the island portions are approximately 22.0 to 32.0%, approximately 22.0 to 28.0%, approximately 24.0 to 32.0%, and approximately 24.0 to 28.0%.
[0080] In addition, in the adhesive film 1 for metal terminals of the present invention, the sea island structure is generally observed in the cross-sectional image before the first polyolefin layer 12a is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, and the cross-sectional image is a cross-sectional image obtained within the range of the surface portion on the substrate 11 side (specifically, from the surface of the substrate 11 side to the portion of 30% thickness) when the thickness of the first polyolefin layer 12a is taken as 100%. The ratio of the total area of the island portions of the sea island structure in the cross-sectional image of the surface portion on the substrate 11 side of the first polyolefin layer 12a before heating is not particularly limited, but is preferably about 26.0% or more, and more preferably about 28.0% or more. In addition, the ratio of the total area of the island portions is preferably about 35.0% or less, and more preferably about 32.0% or less. The preferred range of the ratio of the total area of the island portions is about 26.0 to 35.0%, about 26.0 to 32.0%, about 28.0 to 35.0%, and about 28.0 to 32.0%.
[0081] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the metal terminal 2 side after the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the average particle size of the island portion as the island structure is preferably about 0.3 μm or more, and more preferably about 0.4 μm or more. In addition, the average particle size of the island portion is preferably about 0.6 μm or less, and more preferably about 0.5 μm or less. In addition, as a preferred range of the average particle size of the island portion, about 0.3 to 0.6 μm, about 0.3 to 0.5 μm, about 0.4 to 0.6 μm, and about 0.4 to 0.5 μm can be listed.
[0082] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the substrate 11 side after the adhesive film for metal terminals is heated at a temperature of 190°C and a surface pressure of 0.016MPa for 12 seconds, the average particle size of the island portion as the island structure is preferably about 0.3μm or more, and more preferably about 0.4μm or more. In addition, the average particle size of the island portion is preferably about 0.6μm or less, and more preferably about 0.5μm or less. In addition, as a preferred range of the average particle size of the island portion, about 0.3 to 0.6μm, about 0.3 to 0.5μm, about 0.4 to 0.6μm, and about 0.4 to 0.5μm can be listed.
[0083] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the metal terminal 2 side before the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the average particle size of the island portion as the sea island structure is preferably about 0.2 μm or more, and more preferably about 0.3 μm or more. In addition, the average particle size of the island portion is preferably about 0.5 μm or less, and more preferably about 0.4 μm or less. In addition, as a preferred range of the average particle size of the island portion, about 0.2 to 0.5 μm, about 0.2 to 0.4 μm, about 0.3 to 0.5 μm, and about 0.3 to 0.4 μm can be listed.
[0084] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the substrate 11 side before the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the average particle size of the island portion as the island structure is preferably about 0.3 μm or more, and more preferably about 0.4 μm or more. In addition, the average particle size of the island portion is preferably about 0.6 μm or less, and more preferably about 0.5 μm or less. In addition, as a preferred range of the average particle size of the island portion, about 0.3 to 0.6 μm, about 0.3 to 0.5 μm, about 0.4 to 0.6 μm, and about 0.4 to 0.5 μm can be listed.
[0085] The average particle size of the island portion in the cross-sectional image is a value calculated using the image analysis software ImageJ.
[0086] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the metal terminal 2 side after the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the particle size deviation σ of the island portion as the island structure is preferably 0.4 or less, and more preferably about 0.3 or less. In addition, the particle size deviation σ of the island portion is, for example, 0.1 or more. In addition, as a preferred range of the particle size deviation σ of the island portion, about 0.1 to 0.4 and about 0.1 to 0.3 can be listed.
[0087] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the substrate 11 side after the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the particle size deviation σ of the island portion as the island structure is preferably 0.4 or less, and more preferably about 0.3 or less. In addition, the particle size deviation σ of the island portion is, for example, 0.1 or more. In addition, as a preferred range of the particle size deviation σ of the island portion, about 0.1 to 0.4 and about 0.1 to 0.3 can be listed.
[0088] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the metal terminal 2 side before the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the particle size deviation σ of the island portion as the island structure is preferably 0.4 or less, and more preferably about 0.3 or less. In addition, the particle size deviation σ of the island portion is, for example, 0.1 or more. In addition, as a preferred range of the particle size deviation σ of the island portion, about 0.1 to 0.4 and about 0.1 to 0.3 can be listed.
[0089] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the substrate 11 side before the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the particle size deviation σ of the island portion as the island structure is preferably 0.5 or less, and more preferably about 0.4 or less. In addition, the particle size deviation σ of the island portion is, for example, 0.1 or more. In addition, as a preferred range of the particle size deviation σ of the island portion, about 0.1 to 0.5 and about 0.1 to 0.4 can be listed.
[0090] The particle size deviation σ of the island portion in the cross-sectional image is a value calculated using the image analysis software ImageJ.
[0091] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the metal terminal 2 side after the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the roundness of the island portion as the island structure is preferably 0.75 or more, and more preferably about 0.80 or more. In addition, the roundness of the island portion is, for example, 0.95 or less. In addition, as a preferred range of the roundness of the island portion, about 0.75 to 0.95 and about 0.80 to 0.95 can be listed.
[0092] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the substrate 11 side after the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the roundness of the island portion as the island structure is preferably 0.72 or more, and more preferably about 0.75 or more. In addition, the roundness of the island portion is, for example, 0.95 or less. In addition, as a preferred range of the roundness of the island portion, about 0.72 to 0.95 and about 0.75 to 0.95 can be listed.
[0093] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the metal terminal 2 side before the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the roundness of the island portion as the island structure is preferably 0.55 or more, and more preferably about 0.60 or more. In addition, the roundness of the island portion is, for example, 0.95 or less. In addition, as a preferred range of the roundness of the island portion, about 0.55 to 0.95 and about 0.60 to 0.95 can be listed.
[0094] In addition, in the adhesive film 1 for metal terminals of the present invention, in the above cross-sectional image of the surface portion of the substrate 11 side before the adhesive film for metal terminals is heated at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the roundness of the island portion as the island structure is preferably 0.55 or more, more preferably about 0.60 or more. In addition, the roundness of the island portion is, for example, 0.95 or less. In addition, as a preferred range of the roundness of the island portion, about 0.55 to 0.95 and about 0.60 to 0.95 can be listed.
[0095] The circularity of the island portion in the cross-sectional image is a value calculated using the image analysis software ImageJ.
[0096] The ratio of the total area of the island portions in the sea-island structure of the cross-section of the first polyolefin layer of the adhesive film for metal terminals of the present invention, the average particle size of the island portions, the particle size deviation σ of the island portions and the roundness of the island portions can be adjusted by the composition, skeleton, dispersibility, molecular weight, melting point, MFR of the resin constituting the first polyolefin layer, and the conditions of the T-die, blow molding, etc. in the manufacture of the adhesive film 1 for metal terminals (for example, the width extruded from the T-die, the stretching ratio, the stretching speed, the heat treatment temperature, and the linear speed during extrusion, the cooling speed, the extrusion temperature, etc.).
[0097] As the total thickness of the adhesive film 1 for metal terminals of the present invention, from the viewpoint of improving the adhesion with the above-mentioned metal terminal 2 and appropriately suppressing the decrease in adhesion caused by the electrolyte, for example, it is about 60 μm or more, preferably about 80 μm or more, preferably about 100 μm or more, more preferably about 120 μm or more, and further preferably about 150 μm or more. In addition, the total thickness of the adhesive film 1 for metal terminals of the present invention is preferably about 200 μm or less, more preferably 180 μm or less. As the preferred range of the total thickness of the adhesive film 1 for metal terminals of the present invention, about 60 to 200 μm, about 60 to 180 μm, about 80 to 200 μm, about 80 to 180 μm, about 100 to 200 μm, about 100 to 180 μm, about 120 to 200 μm, about 120 to 180 μm, about 150 to 200 μm, about 150 to 180 μm. As a more specific example, when the adhesive film 1 for metal terminals of the present invention is used for a consumer power storage device, the total thickness is preferably about 60 to 100 μm, and when used for a vehicle-mounted power storage device, the total thickness is preferably about 100 to 200 μm.
[0098] Hereinafter, the first polyolefin layer 12 a , the second polyolefin layer 12 b , and the substrate 11 will be described in detail.
[0099] [First polyolefin layer 12a and second polyolefin layer 12b]
[0100] The adhesive film 1 for metal terminal of the present invention is as follows Figure 4 and Figure 5 As shown in the figure, the substrate 11 has a first polyolefin layer 12a on one side and a second polyolefin layer 12b on the other side. The first polyolefin layer 12a is arranged on the metal terminal 2 side. In addition, the second polyolefin layer 12b is arranged on the outer packaging material 3 side for the storage device. In the adhesive film 1 for metal terminals of the present invention, the first polyolefin layer 12a and the second polyolefin layer 12b are respectively located on the surfaces of the two sides.
[0101] The description of the sea-island structure of the cross-sectional image of the first polyolefin layer 12 a disposed on the metal terminal 2 side is as described above.
[0102] In the adhesive film 1 for metal terminals of the present invention, the first polyolefin layer 12a and the second polyolefin layer 12b are layers respectively comprising polyolefin resins. As polyolefin resins, polyolefins, acid-modified polyolefins, etc. can be cited. The first polyolefin layer 12a preferably comprises an acid-modified polyolefin in the polyolefin resin, and more preferably a layer formed by an acid-modified polyolefin. In addition, the second polyolefin layer 12b preferably comprises a polyolefin or an acid-modified polyolefin in the polyolefin resin, more preferably comprises a polyolefin, and further preferably a layer formed by a polyolefin. Acid-modified polyolefins have a high affinity for metals. In addition, polyolefins have a high affinity for heat-melting resins such as polyolefins. Therefore, in the adhesive film 1 for metal terminals of the present invention, by configuring the first polyolefin layer 12a formed by an acid-modified polyolefin on the side of the metal terminal 2, it is possible to exert a more excellent adhesion at the interface between the adhesive film 1 for metal terminals and the metal terminal 2. Furthermore, by arranging the second polyolefin layer 12 b made of polyolefin on the thermally fusible resin layer 35 side of the power storage device packaging material 3 , it is possible to exhibit better adhesion at the interface between the adhesive film 1 for metal terminal and the thermally fusible resin layer 35 .
[0103] Specific examples of preferred laminated structures of the adhesive film 1 for metal terminals of the present invention include: a three-layer structure in which a first polyolefin layer formed by acid-modified polypropylene / a substrate formed by polypropylene / a second polyolefin layer formed by polypropylene are laminated in sequence; a three-layer structure in which a first polyolefin layer formed by acid-modified polypropylene / a substrate formed by polypropylene / a second polyolefin layer formed by acid-modified polypropylene are laminated in sequence, etc. Among these, a three-layer structure in which a first polyolefin layer formed by acid-modified polypropylene / a substrate formed by polypropylene / a second polyolefin layer formed by polypropylene are laminated in sequence is particularly preferred.
[0104] The acid-modified polyolefin is not particularly limited as long as it is an acid-modified polyolefin, and preferably, a polyolefin graft-modified with an unsaturated carboxylic acid or an anhydride thereof is used.
[0105] Specifically, examples of the acid-modified polyolefin include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; crystalline or amorphous polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); terpolymers of ethylene-butene-propylene, etc. Among these polyolefins, polyethylene and polypropylene are preferred, and polypropylene is particularly preferred.
[0106] In addition, the acid-modified polyolefin may be a cyclic polyolefin. For example, the carboxylic acid-modified cyclic polyolefin is a polymer obtained by replacing part of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or its anhydride, copolymerizing, or block-polymerizing or graft-polymerizing an α,β-unsaturated carboxylic acid or its anhydride with a cyclic polyolefin.
[0107] The acid-modified cyclic polyolefin is a copolymer of an olefin and a cyclic monomer. Examples of olefins that are structural monomers of the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. In addition, examples of cyclic monomers that are structural monomers of the cyclic polyolefin include cyclic olefins such as norbornene; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornene. Among these polyolefins, cyclic olefins are preferably cited, and norbornene is further preferably cited. Styrene can also be cited as a structural monomer.
[0108] Examples of the carboxylic acid or its anhydride used for acid modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, itaconic anhydride, etc. The first polyolefin layer 12a preferably has a peak derived from maleic anhydride when analyzed by infrared spectroscopy. For example, when the maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak at a wave number of 1760 cm -1 Nearby and wave number 1780cm -1 In the case where the first polyolefin layer 12a or the second polyolefin layer 12b is a layer composed of maleic anhydride-modified polyolefin, when measured by infrared spectroscopy, a peak from maleic anhydride is detected. However, if the acid modification degree is low, the peak sometimes becomes smaller and cannot be detected. In this case, it is possible to analyze by nuclear magnetic resonance spectroscopy.
[0109] The first polyolefin layer 12a and the second polyolefin layer 12b can be formed by one resin component alone, or by a blended polymer combining two or more resin components. Moreover, the first polyolefin layer 12a and the second polyolefin layer 12b can be formed by only one layer, or by two or more layers of the same or different resin components. From the viewpoint of the film-forming properties of the first polyolefin layer 12a and the second polyolefin layer 12b, these layers are preferably formed by a blended polymer combining two or more resin components. In the case of making a blended polymer, with respect to the first polyolefin layer 12a, it is preferred that acid-modified polypropylene is the main component (a component of 50% by mass or more), and 50% by mass or less is other resins (preferably polyethylene). In addition, with respect to the second polyolefin layer 12b, it is preferred that polypropylene is the main component (a component of 50% by mass or more), and 50% by mass or less is other resins (preferably polyethylene). On the other hand, from the viewpoint of electrolyte resistance of the first polyolefin layer 12a and the second polyolefin layer 12b, the first polyolefin layer 12a preferably contains acid-modified polypropylene as a single resin, and the second polyolefin layer 12b preferably contains polypropylene as a single resin.
[0110] Moreover, the first polyolefin layer 12a and the second polyolefin layer 12b may contain fillers as needed. Since the first polyolefin layer 12a and the second polyolefin layer 12b contain fillers, the fillers function as separators (spacers), and therefore, the short circuit between the metal terminal 2 and the barrier layer 33 of the outer packaging material 3 for the storage device can be effectively suppressed. As the particle size of the filler, about 0.1 to 35 μm can be listed, preferably about 5.0 to 30 μm, and more preferably about 10 to 25 μm. In addition, as the content of the filler, about 5 to 30 parts by mass can be listed, and more preferably about 10 to 20 parts by mass, relative to 100 parts by mass of the resin component forming the first polyolefin layer 12a and the second polyolefin layer 12b.
[0111] As filler, both inorganic and organic systems can be used. As inorganic filler, for example, carbon (charcoal, graphite), silicon dioxide, aluminum oxide, barium titanate, iron oxide, silicon carbide, zirconium oxide, zirconium silicate, magnesium oxide, titanium oxide, calcium aluminate, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, etc. can be listed. In addition, as organic filler, for example, fluorine-containing resin, phenolic resin, urea resin, epoxy resin, acrylic resin, benzoguanamine-formaldehyde condensate, melamine-formaldehyde condensate, polymethyl methacrylate crosslinked product, polyethylene crosslinked product, etc. can be listed. From the aspect of shape stability, rigidity, and content tolerance, aluminum oxide, silicon dioxide, fluorine-containing resin, acrylic resin, benzoguanamine-formaldehyde condensate are preferred, wherein, spherical aluminum oxide and silicon dioxide are particularly preferred. The method of mixing the filler into the resin component forming the first polyolefin layer 12a and the second polyolefin layer 12b can be: a method of preliminarily melt-blending the two using a Banbury mixer or the like to make a masterbatch, and setting the masterbatch material to a specified mixing ratio; a method of directly mixing with the resin component, etc.
[0112] In addition, the first polyolefin layer 12a and the second polyolefin layer 12b can contain pigments as needed. As the pigment, various inorganic pigments can be used. As a specific example of the pigment, carbon (charcoal, graphite) exemplified in the above-mentioned filler is preferably exemplified. Carbon (charcoal, graphite) is a material usually used inside the storage device, and there is no concern about the dissolution of the electrolyte. In addition, the coloring effect is good, and a sufficient coloring effect can be obtained with an amount added that does not damage the adhesion, and it will not melt due to heat, and the apparent melt viscosity of the resin after addition can be increased. In addition, it prevents the pressurized portion from becoming thinner during thermal bonding (heat sealing), and can impart excellent sealing between the outer packaging material for the storage device and the metal terminal.
[0113] When a pigment is added to the first polyolefin layer 12a and the second polyolefin layer 12b, as the amount thereof added, for example, when carbon black having a particle size of about 0.03 μm is used, about 0.05 to 0.3 parts by mass can be cited, preferably about 0.1 to 0.2 parts by mass, relative to 100 parts by mass of the resin component forming the first polyolefin layer 12a and the second polyolefin layer 12b. By adding a pigment to the first polyolefin layer 12a and the second polyolefin layer 12b, the presence or absence of the adhesive film 1 for metal terminals can be detected by a sensor, or can be visually inspected. It is particularly preferred that the first polyolefin layer 12a contains a pigment. In addition, when a filler and a pigment are added to the first polyolefin layer 12a and the second polyolefin layer 12b, the filler and the pigment can be added to the same layer in the first polyolefin layer 12a and the second polyolefin layer 12b, but from the viewpoint of not damaging the thermal fusion property of the adhesive film 1 for metal terminals, it is preferred that the filler and the pigment are added separately to the first polyolefin layer 12a and the second polyolefin layer 12b.
[0114] The thickness of the first polyolefin layer 12a and the second polyolefin layer 12b is preferably about 10 μm or more, more preferably about 15 μm or more, further preferably about 20 μm or more, and further preferably about 30 μm or more, from the viewpoint of improving the adhesion with the metal terminal 2 and appropriately suppressing the decrease in adhesion due to the electrolyte, and is, for example, about 80 μm or less, preferably about 60 μm or less, and more preferably about 50 μm or less. The preferred range of the thickness of the first polyolefin layer 12a and the second polyolefin layer 12b is about 10 to 80 μm, about 10 to 60 μm, about 10 to 50 μm, about 15 to 80 μm, about 15 to 60 μm, about 15 to 50 μm, about 20 to 80 μm, about 20 to 60 μm, about 20 to 50 μm, about 30 to 80 μm, about 30 to 60 μm, and about 30 to 50 μm. As a more specific example, for example, when the adhesive film 1 for metal terminals of the present invention is used in a storage device for civilian use, the thickness of the first polyolefin layer 12a and the second polyolefin layer 12b are preferably about 10 to 30 μm, respectively, and when used in a storage device for vehicle use, they are preferably about 30 to 80 μm, respectively.
[0115] The ratio of the thickness of the substrate 11 to the total thickness of the first polyolefin layer 12a and the second polyolefin layer 12b is preferably about 0.3 or more, more preferably about 0.4 or more, and further preferably about 0.5 or more, from the viewpoint of improving the close adhesion with the above-mentioned metal terminal 2 and appropriately suppressing the reduction in close adhesion caused by the electrolyte. In addition, it is preferably about 1.0 or less, and more preferably about 0.8 or less. As preferred ranges, there can be listed about 0.3 to 1.0, about 0.3 to 0.8, about 0.4 to 1.0, about 0.4 to 0.8, about 0.5 to 1.0, and about 0.5 to 0.8.
[0116] When the total thickness of the adhesive film for metal terminal 1 is taken as 100%, the ratio of the total thickness of the first polyolefin layer 12a and the second polyolefin layer 12b is preferably about 30 to 80%, more preferably about 50 to 70%.
[0117] [Substrate 11]
[0118] In the adhesive film for metal terminal 1 , the base material 11 is a layer that functions as a support body of the adhesive film for metal terminal 1 .
[0119] There is no particular restriction on the raw material forming the substrate 11. As the raw material forming the substrate 11, for example, polyolefin resins, polyamide resins, polyester resins, epoxy resins, acrylic resins, fluorine-containing resins, silicone resins, phenolic resins, polyetherimides, polyimides, polycarbonates, and mixtures or copolymers thereof, etc. can be cited. Among these, polyolefin resins are particularly preferred. That is, the raw material forming the substrate 11 is preferably a resin containing a polyolefin skeleton, such as polyolefin and acid-modified polyolefin. The resin constituting the substrate 11 contains a polyolefin skeleton, which can be analyzed, for example, by infrared spectroscopy, gas chromatography-mass spectrometry, etc.
[0120] As described above, the substrate 11 preferably includes a polyolefin resin, preferably includes a polyolefin, and more preferably includes a layer formed by a polyolefin. As polyolefins, specifically, polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene can be listed; crystalline or amorphous polypropylenes such as homopolypropylene, block copolymers of polypropylene (such as block copolymers of propylene and ethylene), and random copolymers of polypropylene (such as random copolymers of propylene and ethylene); terpolymers of ethylene-butene-propylene, etc. Among these polyolefins, polyethylene and polypropylene are preferably listed, and polypropylene is more preferably listed. In addition, from the aspect of excellent electrolyte resistance, the substrate 11 preferably includes homopolypropylene, and is particularly preferably formed by homopolypropylene.
[0121] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymers such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid and T represents terephthalic acid) containing structural units derived from terephthalic acid and / or isophthalic acid; and aromatic polyamides such as poly(m-xylylene adipamide) (MXD6); alicyclic polyamides such as polyaminomethylcyclohexyl adipamide (PACM6); and polyamides obtained by copolymerizing a lactam component or an isocyanate component such as 4,4'-diphenylmethane-diisocyanate; polyester amide copolymers or polyetheresteramide copolymers which are copolymers of a copolyamide and a polyester or a polyalkylene ether glycol; and copolymers thereof. These polyamides may be used alone or in combination of two or more.
[0122] Specific examples of the polyester include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, copolyesters containing ethylene terephthalate as a main repeating unit, and copolyesters containing butylene terephthalate as a main repeating unit. In addition, as copolyesters with ethylene terephthalate as the main body of repeating units, specific examples include copolyesters with ethylene terephthalate as the main body of repeating units and obtained by polymerization with ethylene isophthalate (hereinafter abbreviated as poly(terephthalic acid / isophthalic acid) glycol), poly(terephthalic acid / isophthalic acid) glycol, poly(terephthalic acid / adipate) glycol, poly(terephthalic acid / sodium sulfoisophthalate) glycol, poly(terephthalic acid / sodium isophthalate) glycol, poly(terephthalic acid / phenyl-dicarboxylic acid) glycol, poly(terephthalic acid / decanedicarboxylic acid) glycol, and the like. In addition, specific examples of the copolyester having butylene terephthalate as a main repeating unit include a copolyester having butylene terephthalate as a main repeating unit and polymerized with butylene isophthalate (hereinafter referred to as poly(butylene terephthalate / isophthalate)), poly(butylene terephthalate / adipate), poly(butylene terephthalate / sebacate), poly(butylene terephthalate / decanedicarboxylate), polybutylene naphthalate, etc. These polyesters may be used alone or in combination of two or more.
[0123] In addition, the substrate 11 may be formed of a nonwoven fabric formed of the above-mentioned resin. When the substrate 11 is a nonwoven fabric, the substrate 11 is preferably composed of the above-mentioned polyolefin resin, polyamide resin, or the like.
[0124] In addition, by adding a colorant to the substrate 11, the substrate 11 can also be made into a layer containing a colorant. In addition, a resin with low transparency can also be selected to adjust the light transmittance. In the case where the substrate 11 is a film, a colored film or a film with low transparency can also be used. In addition, in the case where the substrate 11 is a non-woven fabric, a non-woven fabric using fibers and an adhesive containing a colorant or a non-woven fabric with low transparency can be used.
[0125] When the substrate 11 is composed of a resin film, the surface of the substrate 11 may be subjected to a known adhesion-facilitating means such as a corona discharge treatment, an ozone treatment, or a plasma treatment, as necessary.
[0126] Regarding the thickness of the substrate 11, from the viewpoint of improving the adhesion with the above-mentioned metal terminal 2 and appropriately suppressing the decrease in adhesion caused by the electrolyte, it is, for example, about 100 μm or less, preferably about 60 μm or less, and more preferably about 55 μm or less. In addition, the thickness of the substrate 11 is preferably about 20 μm or more, more preferably about 30 μm or more, and further preferably about 40 μm or more. As the preferred range of the thickness of the substrate 11, about 20 to 100 μm, about 20 to 60 μm, about 20 to 55 μm, about 30 to 100 μm, about 30 to 60 μm, about 30 to 55 μm, about 40 to 100 μm, about 40 to 60 μm, about 40 to 55 μm can be listed. As a more specific example, when the adhesive film 1 for metal terminals of the present invention is used for a consumer power storage device, the thickness of the substrate 11 is preferably about 30 to 55 μm, and when used for a vehicle-mounted power storage device, it is preferably about 40 to 100 μm.
[0127] [Adhesion promoter layer 13]
[0128] The adhesion promoter layer 13 is a layer provided as needed in order to firmly bond the substrate 11 to the first polyolefin layer 12a and the second polyolefin layer 12b (see Figure 5 The adhesion promoter layer 13 may be provided only on one side between the substrate 11 and the first polyolefin layer 12a and the second polyolefin layer 12b, or may be provided on both sides.
[0129] The adhesion promoter layer 13 can be formed using known adhesion promoters such as isocyanate, polyethyleneimine, polyester, polyurethane, and polybutadiene. From the viewpoint of further improving electrolyte resistance, it is preferably formed by an isocyanate adhesion promoter. As an isocyanate adhesion promoter, an adhesion promoter composed of an isocyanate component selected from triisocyanate monomers and polymerized MDI has excellent lamination strength, and the reduction of lamination strength after electrolyte immersion is small. In particular, it is particularly preferred that the adhesive agent be formed from triphenylmethane-4,4',4"-triisocyanate as a triisocyanate monomer or polymethylene polyphenyl polyisocyanate (NCO content of about 30% and viscosity of 200 to 700 mPa·s) as polymeric MDI. In addition, it is also preferred that the adhesive agent be formed from tri(p-isocyanatephenyl)thiophosphate as a triisocyanate monomer or a two-component curing type adhesive agent having a polyethyleneimine system as a main agent and polycarbodiimide as a crosslinking agent.
[0130] The adhesion promoter layer 13 can be formed by coating and drying using a known coating method such as a bar coating method, a roll coating method, or a gravure coating method. The coating amount of the adhesion promoter is 20 to 100 mg / m2 in the case of an adhesion promoter composed of triisocyanate.2 About 40 to 60 mg / m 2 In the case of an adhesion promoter composed of polymeric MDI, it is 40 to 150 mg / m 2 About 60 to 100 mg / m 2 In the case of a two-liquid curing type adhesion promoter with polyethylene imine as the main agent and polycarbodiimide as the crosslinking agent, 5 to 50 mg / m 2 About 10 to 30 mg / m 2 Among them, the triisocyanate monomer is a monomer having three isocyanate groups in one molecule, and the polymeric MDI is a mixture of MDI and an MDI oligomer obtained by polymerizing MDI, and is represented by the following formula.
[0131]
[0132] The adhesive film 1 for metal terminals of the present invention can be manufactured, for example, by laminating the first polyolefin layer 12a and the second polyolefin layer 12b on both surfaces of the substrate 11. The lamination of the substrate 11 and the first polyolefin layer 12a and the second polyolefin layer 12b can be laminated by a known method such as an extrusion lamination method and a heat lamination method. In addition, when the substrate 11 and the first and second polyolefin layers 12a and 12 are laminated via the adhesion promoter layer 13, for example, the adhesion promoter constituting the adhesion promoter layer 13 is applied and dried on the substrate 11 according to the above method, and the first polyolefin layer 12a and the second polyolefin layer 12b are laminated on the adhesion promoter layer 13.
[0133] There is no particular limitation on the method of making the adhesive film 1 for metal terminals exist between the metal terminals 2 and the outer packaging material 3 for power storage devices. For example, Figures 1 to 3 As shown, at the portion where the metal terminal 2 is clamped by the outer packaging material 3 for the storage device, the adhesive film 1 for the metal terminal is wound on the metal terminal 2. In addition, although the illustration is omitted, at the portion where the metal terminal 2 is clamped by the outer packaging material 3 for the storage device, the adhesive film 1 for the metal terminal can be arranged on both sides of the metal terminal 2 in a manner spanning the two metal terminals 2.
[0134] [Metal terminal 2]
[0135] The adhesive film 1 for metal terminals of the present invention is used between a metal terminal 2 and an outer packaging material 3 for an electrical storage device. The metal terminal 2 (tab) is a conductive component electrically connected to an electrode (positive electrode or negative electrode) of an electrical storage device element 4 and is made of a metal material. There are no particular restrictions on the metal material constituting the metal terminal 2, and examples thereof include aluminum, nickel, copper, and the like. For example, the metal terminal 2 connected to the positive electrode of a lithium-ion electrical storage device is usually made of aluminum or the like. In addition, the metal terminal 2 connected to the negative electrode of a lithium-ion electrical storage device is usually made of copper, nickel, or the like.
[0136] From the viewpoint of improving electrolyte resistance, it is preferred to perform chemical surface treatment on the surface of the metal terminal 2. For example, when the metal terminal 2 is formed of aluminum, as a specific example of chemical surface treatment, a known method of forming a corrosion-resistant film of phosphate, chromate, fluoride, triazine thiol compound, etc. can be cited. Among the methods for forming the corrosion-resistant film, it is preferred to use a phosphate chromate treatment of a material composed of three components: a phenolic resin, a chromium (III) fluoride compound, and phosphoric acid.
[0137] The size of the metal terminal 2 can be appropriately set according to the size of the power storage device used. As the thickness of the metal terminal 2, about 50 to 1000 μm is preferred, and about 70 to 800 μm is more preferred. In addition, as the length of the metal terminal 2, about 1 to 200 mm is preferred, and about 3 to 150 mm is more preferred. In addition, as the width of the metal terminal 2, about 1 to 200 mm is preferred, and about 3 to 150 mm is more preferred.
[0138] [Outer packaging materials for power storage devices 3]
[0139] As the outer packaging material 3 for the power storage device, there can be mentioned a material having a laminated structure composed of a laminated body having at least a base layer 31, a barrier layer 33 and a heat-fusible resin layer 35 in this order. Figure 6 In the figure, as an example of the cross-sectional structure of the outer packaging material 3 for a storage device, a substrate layer 31, an adhesive layer 32 provided as required, a barrier layer 33, an adhesive layer 34 provided as required, and a heat-fusible resin layer 35 are stacked in this order. In the outer packaging material 3 for a storage device, the substrate layer 31 is the outer layer side, and the heat-fusible resin layer 35 is the innermost layer. When assembling the storage device, the heat-fusible resin layers 35 located at the periphery of the storage device element 4 are brought into surface contact with each other and heat-fused to seal the storage device element 4, thereby encapsulating the storage device element 4. In addition, in Figures 1 to 3In the figure, the storage device 10 is shown in which an embossed storage device outer packaging material 3 is used, but the storage device outer packaging material 3 may be an unformed pocket type. Among them, the pocket type includes three-way sealed, four-way sealed, pillow type, etc., and any type is acceptable.
[0140] There is no particular restriction on the thickness of the laminate constituting the outer packaging material 3 for storage device. As for the upper limit, from the viewpoints of cost reduction and energy density improvement, preferably, about 190 μm or less, about 180 μm or less, about 160 μm or less, about 155 μm or less, about 140 μm or less, about 130 μm or less, about 120 μm or less are listed; as for the lower limit, from the viewpoint of maintaining the function of the outer packaging material 3 for storage device such as protecting the storage device element 4, preferably, about 35 μm or more, about 45 μm or more, about 60 μm or more, about 80 μm or more are listed; as for the preferred range, for example, about 35 to 190 μm, about 35 to 180 μm, about 35 to 160 μm, about 35 to 155 μm, about 35 to 14 ... 0μm, about 35-130μm, about 35-120μm, about 45-190μm, about 45-180μm, about 45-160μm, about 45-155μm, about 45-140μm, about 45-130μm, about 45-120μm, about 60-190μm, about 60-180μm, about 60-160μm, about 60-155μm, about 60-140μm, about 60-130μm, about 60-120μm, about 80-190μm, about 80-180μm, about 80-160μm, about 80-155μm, about 80-140μm, about 80-130μm, about 80-120μm.
[0141] (Base material layer 31)
[0142] In the electricity storage device packaging material 3 , the base material layer 31 is a layer that functions as a base material of the electricity storage device packaging material and is a layer forming the outermost layer side.
[0143] There are no particular restrictions on the raw materials for forming the substrate layer 31 as long as they have insulating properties. Examples of the raw materials for forming the substrate layer 31 include polyester, polyamide, epoxy resin, acrylic resin, fluorine-containing resin, polyurethane, silicone resin, phenolic resin, polyetherimide, polyimide, and mixtures or copolymers thereof. Polyesters such as polyethylene terephthalate and polybutylene terephthalate have advantages such as excellent resistance to electrolyte and difficulty in whitening due to the adhesion of electrolyte, and are suitable for use as raw materials for forming the substrate layer 31. In addition, polyamide films have excellent stretchability and can prevent the substrate layer 31 from whitening due to resin rupture during molding, and are suitable for use as raw materials for forming the substrate layer 31.
[0144] The substrate layer 31 may be formed of a uniaxially stretched or biaxially stretched resin film or an unstretched resin film. Among them, a uniaxially stretched or biaxially stretched resin film, especially a biaxially stretched resin film, has improved heat resistance due to oriented crystallization, and is therefore suitable for use as the substrate layer 31.
[0145] Among these, as the resin film forming the base material layer 31, preferably nylon and polyester are used, and more preferably biaxially stretched nylon and biaxially stretched polyester are used.
[0146] In order to improve the pinhole resistance and the insulation when the packaging body of the storage device is made, the base layer 31 can also be a laminate of resin films of different raw materials. Specifically, a multilayer structure formed by laminating a polyester film and a nylon film, and a multilayer structure formed by laminating a biaxially stretched polyester and a biaxially stretched nylon, etc. can be cited. In the case of making the base layer 31 a multilayer structure, each resin film can be bonded by an adhesive or directly laminated without using an adhesive. In the case of bonding without using an adhesive, for example, a method of bonding in a hot melt state such as a coextrusion method, a sandwich lamination method, and a hot lamination method can be cited.
[0147] In addition, in order to improve the formability, the base layer 31 may also be subjected to low friction. When the base layer 31 is subjected to low friction, the friction coefficient of the surface thereof is not particularly limited, and for example, it may be 1.0 or less. In order to cause the base layer 31 to be subjected to low friction, for example, matte treatment, formation of a thin film layer of a lubricant, or a combination thereof may be used.
[0148] The thickness of the base material layer 31 is, for example, about 10 to 50 μm, preferably about 15 to 30 μm.
[0149] (Adhesive layer 32)
[0150] In the power storage device packaging material 3 , the adhesive layer 32 is a layer disposed on the base layer 31 as necessary in order to impart adhesion to the base layer 31 . That is, the adhesive layer 32 is provided between the base layer 31 and the barrier layer 33 .
[0151] The adhesive layer 32 is formed of an adhesive capable of bonding the substrate layer 31 to the barrier layer 33. The adhesive used to form the adhesive layer 32 may be a two-component curing adhesive or a one-component curing adhesive. In addition, there is no particular limitation on the bonding mechanism of the adhesive used to form the adhesive layer 32, and the adhesive may be a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressing type, or the like.
[0152] As the resin component of the adhesive that can be used to form the adhesive layer 32, from the viewpoints of excellent ductility, durability under high humidity conditions and yellowing inhibition, thermal degradation inhibition during heat sealing, and inhibition of the reduction in the lamination strength between the base layer 31 and the barrier layer 33, thereby effectively inhibiting the occurrence of delamination, the following are preferably listed: polyurethane-based two-component curing adhesives; polyamides, polyesters, or blended resins of these with modified polyolefins.
[0153] In addition, the adhesive layer 32 may be multilayered with different adhesive components. In the case where the adhesive layer 32 is multilayered with different adhesive components, from the viewpoint of improving the lamination strength between the substrate layer 31 and the barrier layer 33, it is preferred that a resin having excellent adhesion to the substrate layer 31 is selected as the adhesive component disposed on the substrate layer 31 side, and an adhesive component having excellent adhesion to the barrier layer 33 is selected as the adhesive component disposed on the barrier layer 33 side. In the case where the adhesive layer 32 is multilayered with different adhesive components, specifically, as the adhesive component disposed on the barrier layer 33 side, preferably, acid-modified polyolefins, metal-modified polyolefins, mixed resins of polyesters and acid-modified polyolefins, resins containing copolyesters, and the like are listed.
[0154] The thickness of the adhesive layer 32 is, for example, about 2 to 50 μm, preferably about 3 to 25 μm.
[0155] (Barrier layer 33)
[0156] In the outer packaging material for the storage device, the barrier layer 33 is a layer that improves the strength of the outer packaging material for the storage device and has the function of preventing water vapor, oxygen, light, etc. from invading the interior of the storage device. The barrier layer 33 is preferably a metal layer, that is, a layer formed of metal. As metals constituting the barrier layer 33, aluminum, stainless steel, titanium, etc. can be specifically listed, and aluminum is preferably listed. The barrier layer 33 can be formed, for example, of a metal foil, or a metal vapor-deposited film, an inorganic oxide vapor-deposited film, a carbon-containing inorganic oxide vapor-deposited film, a film provided with these vapor-deposited films, etc., preferably formed of a metal foil, and more preferably formed of an aluminum foil. When manufacturing an outer packaging material for a storage device, from the viewpoint of preventing wrinkles or pinholes from forming in the barrier layer 33, it is more preferable that the barrier layer is formed of a soft aluminum foil, such as annealed aluminum (JIS H4160: 1994A8021H-O, JIS H4160: 1994A8079H-O, JIS H4000: 2014A8021P-O, JIS H4000: 2014A8079P-O).
[0157] The thickness of the barrier layer 33 is preferably about 10 to 200 μm, more preferably about 20 to 100 μm, from the viewpoint of reducing the thickness of the packaging material for a power storage device and preventing pinholes from being generated during molding.
[0158] In addition, the barrier layer 33 is preferably subjected to chemical surface treatment on at least one surface, more preferably both surfaces, for the purpose of stabilizing adhesion, preventing dissolution or corrosion, etc. Here, the chemical surface treatment refers to a treatment for forming a corrosion-resistant film on the surface of the barrier layer.
[0159] (Adhesive layer 34)
[0160] In the power storage device packaging material 3 , the adhesive layer 34 is a layer provided between the barrier layer 33 and the thermally-adhesive resin layer 35 as necessary in order to firmly adhere the thermally-adhesive resin layer 35 .
[0161] The adhesive layer 34 is formed of an adhesive capable of bonding the barrier layer 33 and the heat-fusible resin layer 35. There are no particular restrictions on the composition of the adhesive used to form the adhesive layer, and for example, a resin composition containing an acid-modified polyolefin can be cited. Examples of the acid-modified polyolefin include those exemplified in the first polyolefin layer 12a and the second polyolefin layer 12b.
[0162] The thickness of the adhesive layer 34 is, for example, about 1 to 40 μm, preferably about 2 to 30 μm.
[0163] (Thermal Fusible Resin Layer 35)
[0164] In the electricity storage device packaging material 3 , the heat-fusible resin layer 35 corresponds to the innermost layer, and is a layer in which the heat-fusible resin layers are heat-fused to each other when the electricity storage device is assembled to seal the electricity storage device element.
[0165] The resin component used for the heat-fusible resin layer 35 is not particularly limited as long as it can be heat-fusible, and examples thereof include polyolefins and cyclic polyolefins.
[0166] As the above-mentioned polyolefin, specifically, polyethylene such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene can be cited; crystalline or amorphous polypropylene such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); terpolymers of ethylene-butene-propylene, etc. Among these polyolefins, polyethylene and polypropylene are preferably cited.
[0167] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer. Examples of olefins that are structural monomers of the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, isoprene, and the like. In addition, examples of cyclic monomers that are structural monomers of the cyclic polyolefin include cyclic olefins such as norbornene; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornene can be cited. Among these polyolefins, cyclic olefins are preferably cited, and norbornene is more preferably cited. Styrene can also be cited as a structural monomer.
[0168] Among these resin components, preferred are crystalline or amorphous polyolefins, cyclic polyolefins, and polymer blends thereof; more preferred are polyethylene, polypropylene, copolymers of ethylene and norbornene, and polymer blends of two or more thereof.
[0169] The heat-fusible resin layer 35 may be formed of one resin component alone or of a blended polymer of two or more resin components. Furthermore, the heat-fusible resin layer 35 may be formed of only one layer or of two or more layers of the same or different resin components. When the second polyolefin layer 12b and the heat-fusible resin layer 35 have the same resin, the adhesion between these layers is improved, which is particularly preferred.
[0170] The thickness of the heat-adhesive resin layer 35 is not particularly limited, but is about 2 to 2000 μm, preferably about 5 to 1000 μm, and more preferably about 10 to 500 μm.
[0171] 2. Power storage devices
[0172] The electric storage device 10 of the present invention includes: an electric storage device element 4 having at least a positive electrode, a negative electrode, and an electrolyte; an outer packaging material 3 for an electric storage device that encapsulates the electric storage device element 4; and metal terminals 2 that are electrically connected to the positive electrode and the negative electrode, respectively, and extend to the outside of the outer packaging material 3 for the electric storage device. The electric storage device 10 of the present invention is characterized in that the adhesive film 1 for metal terminals of the present invention is present between the metal terminal 2 and the outer packaging material 3 for the electric storage device. That is, the electric storage device 10 of the present invention can be manufactured by a method including a step of allowing the adhesive film 1 for metal terminals of the present invention to be present between the metal terminal 2 and the outer packaging material 3 for the electric storage device.
[0173] Specifically, a storage device 4 having at least a positive electrode, a negative electrode and an electrolyte is covered with a storage device outer packaging material 3 in a state where metal terminals 2 connected to the positive electrode and the negative electrode are extended outward, respectively, and the adhesive film 1 for metal terminals of the present invention is present between the metal terminals 2 and the heat-fusible resin layer 35, and a flange portion of the storage device outer packaging material (a region where the heat-fusible resin layers 35 are in contact with each other, the peripheral portion 3a of the storage device outer packaging material) is formed at the periphery of the storage device element 4, and the heat-fusible resin layers 35 of the flange portion are heat-sealed to each other to seal, thereby providing a storage device 10 using the storage device outer packaging material 3. In addition, when the storage device outer packaging material 3 is used to accommodate the storage device element 4, the storage device outer packaging material 3 is used in a manner such that the heat-fusible resin layer 35 of the storage device outer packaging material 3 is on the inner side (the side in contact with the storage device element 4).
[0174] The outer packaging material for the storage device of the present invention is suitable for storage devices such as batteries (including capacitors (condensor), capacitors (capacitor) etc.). In addition, the outer packaging material for the storage device of the present invention can be used for any of primary batteries and secondary batteries, preferably secondary batteries. There is no particular restriction on the type of secondary battery to which the outer packaging material for the storage device of the present invention is applicable, for example, lithium ion batteries, lithium ion polymer batteries, all-solid batteries, lead batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, multivalent cation batteries, capacitors (condensor), capacitors (capacitor) etc. can be listed. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries can be listed as preferred applicable objects of the outer packaging material for the storage device of the present invention.
[0175] Example
[0176] Hereinafter, the present invention will be described in detail with reference to Examples and Comparative Examples, but the present invention is not limited to the Examples.
[0177] <Manufacturing of adhesive films for metal terminals>
[0178] Example 1
[0179] As a polyolefin forming the first polyolefin layer, maleic anhydride-modified polypropylene (PPa) was prepared, as a polyolefin forming the second polyolefin layer, polypropylene (PP) was prepared, and as a substrate, an unstretched polypropylene film (CPP, homopolypropylene, thickness 50 μm) was prepared. Maleic anhydride-modified polypropylene (PPa) was extruded on one surface of the substrate (CPP) using a T-die extruder to form a first polyolefin layer (thickness 50 μm), and polypropylene (PP) was extruded on the other surface of the substrate (CPP) using a T-die extruder to form a second polyolefin layer (thickness 50 μm), thereby obtaining an adhesive film for metal terminals having a first polyolefin layer (50 μm, PPa layer) / substrate (50 μm, CPP layer) / second polyolefin layer (50 μm, PP layer) laminated in sequence.
[0180] Comparative Example 1
[0181] As the polyolefin forming the first polyolefin layer, maleic anhydride-modified polypropylene (PPa) was prepared, as the polyolefin forming the second polyolefin layer, polypropylene (PP) was prepared, and as the substrate, a polypropylene film (PP, thickness 30 μm) colored black with carbon black was prepared. Maleic anhydride-modified polypropylene (PPa) was extruded on one surface of the substrate (PP) using a T-die extruder to form a first polypropylene layer (thickness 50 μm), and polypropylene (PP) was extruded on the other surface of the substrate (PP) using a T-die extruder to form a second polypropylene layer (thickness 50 μm), thereby obtaining an adhesive film for metal terminals having a first polyolefin layer (50 μm, PPa layer) / substrate (30 μm, PP layer) / second polyolefin layer (20 μm, PP layer) laminated in sequence.
[0182] Comparative Example 2
[0183] As the polyolefin forming the first polyolefin layer, maleic anhydride-modified polypropylene (PPa) was prepared, as the polyolefin forming the second polyolefin layer, maleic anhydride-modified polypropylene (PPa) was prepared, and as the substrate, polypropylene (PP) was prepared. The resins of each layer were used to perform multi-layer air-cooling blow molding to obtain an adhesive film for metal terminals having a first polyolefin layer (25 μm, PPa layer) / substrate (50 μm, PP layer) / second polyolefin layer (25 μm, PPa layer) laminated in sequence.
[0184] The number of islands in the cross-section of the first polyolefin layer of the adhesive film for metal terminals described in Tables 1 and 2, the ratio of the total area, the average particle size, the particle size deviation and the roundness can be adjusted by the composition, skeleton, dispersibility, molecular weight, melting point, MFR of the resin constituting the first polyolefin layer, and the conditions of T-die, blow molding, etc. (for example, the width extruded from the T-die, the stretching ratio, the stretching speed, the heat treatment temperature, and the line speed during extrusion, the cooling speed, the extrusion temperature, etc.) etc. In Example 1, after heating for 12 seconds (with a surface pressure of 0.016 MPa) using a hot plate heated to a temperature of 190°C described later, it was naturally cooled at room temperature (25°C). The island structure will also change due to the cooling conditions after heating.
[0185] <Observation of the island part in the sea-island structure>
[0186] The metal terminal is embedded in a thermosetting epoxy resin with an adhesive film and cured. A commercially available rotary ultrathin slicer (UC6 manufactured by LEICA) and a diamond knife are used to make a cross section in the target direction (a cross section in the direction parallel to the TD and in the thickness direction). At this time, the cross section is made at -70°C using a cryosectioning method using liquid nitrogen. Together with the embedding resin, it is stained with ruthenium tetroxide overnight. After staining, since polypropylene expands, the expanded part is trimmed using an ultrathin slicer, and 100nm to 300nm are cut off each time in the MD direction, with a total of about 1μm to 2μm cut off, and the exposed cross section is observed as described below. For the stained cross section, a field emission scanning electron microscope (S-4800TYPE1 manufactured by Hitachi High-Technologies Corporation, measurement conditions: 3kV 20mA High WD6mm detector (Upper)) is used to observe and obtain an image (magnification is 10,000 times). In addition, for the surface portion of the first polyolefin layer on the metal terminal side (when the thickness of the first polyolefin layer is 100%, the range from the surface on the opposite side of the substrate side to the portion of 30% thickness, refer to Figure 4), and the surface part of the substrate side of the first polyolefin layer (when the thickness of the first polyolefin layer is taken as 100%, the range from the surface of the substrate side to the part with 30% thickness) are respectively obtained. Next, using image processing software that can binarize the image (image analysis software WinROOF (Ver7.4) manufactured by Mitani Shoji), the island part and the sea part of the sea island structure are binarized in this image, and the number of island parts, the ratio of the total area of the island parts (total area of the island parts / area of the measurement range of the image), the average particle size of the island parts, the particle size deviation σ of the island parts and the roundness of the island parts are respectively calculated. The results are shown in Tables 1 and 2. Table 1 is the measurement result of the sample after heating the adhesive film for metal terminals for 12 seconds using a hot plate heated to 190°C in the same way as in the <Measurement of the adhesion strength between the adhesive film for metal terminals and the metal terminals> described later, and Table 2 is the measurement result of the sample without such heating.
[0187] The binarized cross-sectional images of Example 1 and Comparative Examples 1 and 2 are shown in FIG. Figure 8 to Figure 13 . Figure 8 is the surface portion of the first polyolefin layer on the metal terminal side of Example 1, Fig. 9 is the surface portion of the first polyolefin layer on the substrate side of Example 1, Fig.10 is the surface portion of the first polyolefin layer on the metal terminal side of Comparative Example 1, Fig.11 is the surface portion of the substrate side of the first polyolefin layer of Comparative Example 1, Fig.12 is the surface portion of the first polyolefin layer on the metal terminal side of Comparative Example 2, Fig.13 is the surface portion of the substrate side of the first polyolefin layer of the comparative example. Figure 8 to Figure 13 In each figure, the image on the left is an image before the metal terminal adhesive film is heated at a temperature of 190°C and a surface pressure of 0.016 MPa for 12 seconds, and the image on the right is an image after the metal terminal adhesive film is heated at a temperature of 190°C and a surface pressure of 0.016 MPa for 12 seconds (same as the measurement of the adhesion strength described later, after heating for 12 seconds using a hot plate heated to 190°C and a surface pressure of 0.016 MPa). In addition, in this measurement, since the island part is further dyed than the sea part, the island part appears brighter than the sea part.
[0188] [Image processing conditions]
[0189] Image processing was performed using the image analysis software ImageJ. Specifically, the SEM image was obtained in the form of a digital file of a grayscale image (JPEG), and processed according to the following binarization processing steps and parameters, with the grayscale (bright) pixels above the threshold being output as 1 and the grayscale (dark) pixels below the threshold being output as 0, which were defined as islands and seas, respectively.
[0190] <Binarization>
[0191] 1. Despeckle
[0192] 2. Remove the outline of the island (Remove Outliers radius = 4threshold = 1which = Bright)
[0193] 3. Remove the outline of the sea (Remove Outliers radius = 4threshold = 1which = Dark)
[0194] 4. Despeckle
[0195] 5. Gaussian blur in the X-axis (short side of the sample) direction (threshold = 3 pixels)
[0196] 6. Contrast enhancement (saturated = 0.2)
[0197] 7. Remove the outline of the island (Remove Outliers radius = 4threshold = 1which = Bright)
[0198] 8. Remove the outline of the sea (Remove Outliers radius = 4threshold = 1which = Dark)
[0199] 9. Otsu binarization
[0200] The average particle size of the island portion is a value calculated based on the maximum Feret diameter of the island portion of the image binarized by the image analysis software ImageJ. In addition, the particle size deviation σ of the island portion is a value calculated based on the standard deviation of the average particle size. In addition, the roundness of the island portion is a value calculated by the difference between the radii of the two concentric circles when the interval between the concentric circles becomes the smallest when the island portion of the image binarized by the image analysis software ImageJ is sandwiched between two concentric geometric circles.
[0201] <Measurement of adhesion strength between adhesive film for metal terminal and metal terminal>
[0202] As a metal terminal, aluminum (JIS H4160: 1994A8079H-O) with a length of 50 mm, a width of 22.5 mm, and a thickness of 0.2 mm is prepared. In addition, each adhesive film for metal terminals obtained in the embodiment and the comparative example is cut into a length of 45 mm and a width of 15 mm. Next, the adhesive film for metal terminals is placed on the metal terminal to obtain a laminate of metal terminal / adhesive film. At this time, the metal terminals are laminated in such a manner that the longitudinal and transverse directions of the metal terminals are respectively consistent with the length direction and the width direction of the adhesive film for the metal terminals, and the metal terminal is consistent with the center of the adhesive film for the metal terminals. In addition, the first polyolefin layer of the adhesive film for the metal terminal is arranged on the metal terminal side. Next, a tetrafluoroethylene-ethylene copolymer film (ETFE film, thickness 100 μm) was placed on the adhesive film for metal terminals of the laminate (the surface of the adhesive film for metal terminals was covered with ETFE film), and the laminate was placed on a hot plate heated to 190°C (the metal terminal was on the hot plate side), and a 500g weight with a sponge (surface pressure was 0.016 MPa) was placed, and the adhesive film was thermally welded to the metal terminal. The laminate after thermal welding was naturally cooled to 25°C. Next, the adhesive film for metal terminals was peeled off from the metal terminal using a Tensilon universal material testing machine (RTG-1210 manufactured by A&D) at 25°C. The maximum strength at the time of peeling was taken as the adhesion strength (N / 15mm) to the metal terminal. The peeling speed was set to 50 mm / min, the peeling angle was set to 180°, and the distance between the chucks was set to 30 mm. The measurements were performed 3 times and the average value was taken. The results are shown in Table 1. The treatment of standing for 12 seconds in a heating and pressurizing environment at a temperature of 190° C. and a surface pressure of 0.016 MPa is a treatment that assumes the heat and pressure applied in the above-mentioned preliminary bonding step and main bonding step.
[0203] <Adhesion strength after electrolyte immersion>
[0204] The adhesive film and the metal terminal are heat-fused in the same manner as in the above-mentioned <Measurement of the adhesion strength between the adhesive film for metal terminals and the metal terminal>. The heat-fused laminate is naturally cooled to 25°C. Next, the obtained laminate is immersed in an electrolyte at 85°C (a solution obtained by mixing 1 mol / L of lithium hexafluorophosphate in a solution mixed at a volume ratio of ethylene carbonate: diethyl carbonate: dimethyl carbonate = 1:1:1) for 1 day, and then washed with water until the electrolyte and salt are fully washed away, taken out, and the adhesive film for metal terminals is peeled off from the metal terminal within 1 hour in the same manner as in the above-mentioned <Measurement of the adhesion strength between the adhesive film for metal terminals and the metal terminal>. The maximum strength at the time of peeling is taken as the adhesion strength to the metal terminal (N / 15mm). The results are shown in Table 1.
[0205] [Table 1]
[0206]
[0207] [Table 2]
[0208]
[0209] In the cross-sectional image of the adhesive film for metal terminals of Example 1 after heating the adhesive film for metal terminals at a temperature of 190° C. and a surface pressure of 0.016 MPa for 12 seconds, the ratio of the total area of the island portions of the sea-island structure is set to 25.0 to 35.0%, and the cross-sectional image is the above cross-sectional image of the surface portion on the metal terminal side of the first polyolefin layer. The adhesive film for metal terminals of Example 1 obtained by heat sealing has excellent adhesion to the metal terminal, and even when the electrolyte adheres to the adhesive film that is closely bonded to the metal terminal by heat sealing, the decrease in adhesion to the metal terminal can be appropriately suppressed.
[0210] As described above, the present invention provides the following aspects of the invention.
[0211] Item 1. An adhesive film for metal terminals, which is present between a metal terminal electrically connected to an electrode of an electric storage device element and an outer packaging material for an electric storage device that encapsulates the electric storage device element.
[0212] The adhesive film for metal terminals is composed of a laminated body, which has a first polyolefin layer arranged on the metal terminal side, a substrate, and a second polyolefin layer arranged on the outer packaging material side of the power storage device in this order.
[0213] In a cross-sectional image of the first polyolefin layer taken in a direction parallel to TD and in the thickness direction using a field emission scanning electron microscope, a sea-island structure was observed.
[0214] The cross-sectional image is a cross-sectional image obtained from the surface on the opposite side of the surface on the substrate side to a portion having a thickness of 30% when the thickness of the first polyolefin layer is taken as 100%.
[0215] In the cross-sectional image after the adhesive film for metal terminals is allowed to stand for 12 seconds in a heating and pressurizing environment at a temperature of 190° C. and a surface pressure of 0.016 MPa and then for 1 hour in an environment at a temperature of 25° C., the ratio of the total area of the island portions of the sea-island structure is 25.0% to 35.0%.
[0216] Item 2. The adhesive film for a metal terminal according to Item 1, wherein in the cross-sectional image, an average particle size of the island portion is 0.3 μm or more.
[0217] Item 3. The adhesive film for a metal terminal according to Item 1 or 2, wherein in the cross-sectional image, a deviation in the particle size of the island portion is 0.3 or less.
[0218] Item 4. The adhesive film for a metal terminal according to any one of Items 1 to 3, wherein the circularity of the island portion in the cross-sectional image is 0.75 or more.
[0219] Item 5. The adhesive film for a metal terminal according to any one of Items 1 to 4, wherein the first polyolefin layer has a thickness of 60 μm or less.
[0220] Item 6. The adhesive film for a metal terminal according to any one of Items 1 to 5, wherein the substrate has a thickness of 60 μm or less.
[0221] Item 7. The adhesive film for a metal terminal according to any one of Items 1 to 6, wherein the second polyolefin layer has a thickness of 60 μm or less.
[0222] Item 8. The adhesive film for a metal terminal according to any one of Items 1 to 7, wherein the adhesive film for a metal terminal has a thickness of 180 μm or less.
[0223] Item 9. The adhesive film for a metal terminal according to any one of Items 1 to 8, wherein the first polyolefin layer contains a pigment.
[0224] Item 10. The adhesive film for a metal terminal according to any one of Items 1 to 9, wherein the substrate comprises a polyolefin skeleton.
[0225] Item 11. A method for producing an adhesive film for a metal terminal, wherein the adhesive film for a metal terminal is present between a metal terminal electrically connected to an electrode of an electric storage device element and an outer packaging material for an electric storage device that encapsulates the electric storage device element,
[0226] The adhesive film for metal terminals is composed of a laminated body, which has a first polyolefin layer arranged on the metal terminal side, a substrate, and a second polyolefin layer arranged on the outer packaging material side of the power storage device in this order.
[0227] The production method comprises the step of obtaining a laminate having the first polyolefin layer, the substrate and the second polyolefin layer in this order,
[0228] In a cross-sectional image of the first polyolefin layer taken in a direction parallel to TD and in the thickness direction using a field emission scanning electron microscope, a sea-island structure was observed.
[0229] The cross-sectional image is a cross-sectional image obtained from the surface on the opposite side of the surface on the substrate side to a portion having a thickness of 30% when the thickness of the first polyolefin layer is taken as 100%.
[0230] In the cross-sectional image after the adhesive film for metal terminals is allowed to stand for 12 seconds in a heating and pressurizing environment at a temperature of 190° C. and a surface pressure of 0.016 MPa and then for 1 hour in an environment at a temperature of 25° C., the ratio of the total area of the island portions of the sea-island structure is 25.0% to 35.0%.
[0231] Item 12. A metal terminal with an adhesive film for a metal terminal, wherein the adhesive film for a metal terminal according to any one of Items 1 to 10 is disposed on the metal terminal.
[0232] Item 13. An electric storage device, comprising the electric storage device element having at least a positive electrode, a negative electrode and an electrolyte, the electric storage device outer packaging material encapsulating the electric storage device element, and the metal terminal electrically connected to the positive electrode and the negative electrode respectively and extending to the outside of the electric storage device outer packaging material, wherein:
[0233] The adhesive film for metal terminal described in any one of items 1 to 10 is present between the metal terminal and the outer packaging material for an electric storage device.
[0234] Item 14. A method for manufacturing an electric storage device, the electric storage device comprising the electric storage device element having at least a positive electrode, a negative electrode and an electrolyte, the electric storage device outer packaging material encapsulating the electric storage device element, and the metal terminal electrically connected to the positive electrode and the negative electrode respectively and extending to the outside of the electric storage device outer packaging material, wherein:
[0235] The method comprises the step of allowing the adhesive film for metal terminal according to any one of items 1 to 10 to be interposed between the metal terminal and the electricity storage device packaging material, and packaging the electricity storage device element with the electricity storage device packaging material.
[0236] Explanation of symbols
[0237] 1: Adhesive film for metal terminal; 2: Metal terminal; 3: Outer packaging material for storage device; 3a: Peripheral portion of outer packaging material for storage device; 4: Storage device element; 10: Storage device; 11: Base material; 12a: First polyolefin layer; 12b: Second polyolefin layer; 13: Adhesion promoter layer; 31: Base material layer; 32: Adhesive layer; 33: Barrier layer; 34: Adhesive layer; 35: Thermally fusible resin layer.
Claims
1. An adhesive film for a metal terminal, characterized in that: The adhesive film for metal terminals is present between a metal terminal electrically connected to an electrode of an electric storage device element and an outer packaging material for an electric storage device that seals the electric storage device element. The adhesive film for metal terminals is composed of a laminated body, which has a first polyolefin layer arranged on the metal terminal side, a substrate, and a second polyolefin layer arranged on the outer packaging material side of the power storage device in this order. The ratio of the thickness of the substrate to the total thickness of the first polyolefin layer and the second polyolefin layer is 0.3 or more and 0.8 or less, In a cross-sectional image of the first polyolefin layer taken in a direction parallel to TD and in the thickness direction using a field emission scanning electron microscope, a sea-island structure was observed. The cross-sectional image is a cross-sectional image obtained in a range from the surface on the opposite side to the surface on the substrate side to a portion having a thickness of 30% when the thickness of the first polyolefin layer is taken as 100%. In the cross-sectional image after the adhesive film for metal terminals is allowed to stand for 12 seconds in a heating and pressurizing environment at a temperature of 190° C. and a surface pressure of 0.016 MPa and then allowed to stand for 1 hour in an environment at a temperature of 25° C., the ratio of the total area of the island portions of the sea-island structure is 28.0% or more and 35.0% or less, In the cross-sectional image, the particle size deviation of the island portion is 0.3 or less.
2. An adhesive film for a metal terminal, characterized in that: The adhesive film for metal terminals is present between a metal terminal electrically connected to an electrode of an electric storage device element and an outer packaging material for an electric storage device that seals the electric storage device element. The adhesive film for metal terminals is composed of a laminated body, which has a first polyolefin layer arranged on the metal terminal side, a substrate, and a second polyolefin layer arranged on the outer packaging material side of the power storage device in this order. The ratio of the thickness of the substrate to the total thickness of the first polyolefin layer and the second polyolefin layer is 0.3 or more and 0.8 or less, In a cross-sectional image of the first polyolefin layer taken in a direction parallel to TD and in the thickness direction using a field emission scanning electron microscope, a sea-island structure was observed. The cross-sectional image is a cross-sectional image obtained in a range from the surface on the opposite side to the surface on the substrate side to a portion having a thickness of 30% when the thickness of the first polyolefin layer is taken as 100%. In the cross-sectional image after the adhesive film for metal terminals is allowed to stand for 12 seconds in a heating and pressurizing environment at a temperature of 190° C. and a surface pressure of 0.016 MPa and then allowed to stand for 1 hour in an environment at a temperature of 25° C., the ratio of the total area of the island portions of the sea-island structure is 28.0% or more and 35.0% or less, In the cross-sectional image, the average grain size of the island portion is 0.3 μm or more.
3. An adhesive film for a metal terminal, characterized in that: The adhesive film for metal terminals is present between a metal terminal electrically connected to an electrode of an electric storage device element and an outer packaging material for an electric storage device that seals the electric storage device element. The adhesive film for metal terminals is composed of a laminated body, which has a first polyolefin layer arranged on the metal terminal side, a substrate, and a second polyolefin layer arranged on the outer packaging material side of the power storage device in this order. The ratio of the thickness of the substrate to the total thickness of the first polyolefin layer and the second polyolefin layer is 0.3 or more and 0.8 or less, In a cross-sectional image of the first polyolefin layer taken in a direction parallel to TD and in the thickness direction using a field emission scanning electron microscope, a sea-island structure was observed. The cross-sectional image is a cross-sectional image obtained in a range from the surface on the opposite side to the surface on the substrate side to a portion having a thickness of 30% when the thickness of the first polyolefin layer is taken as 100%. In the cross-sectional image after the adhesive film for metal terminals is allowed to stand for 12 seconds in a heating and pressurizing environment at a temperature of 190° C. and a surface pressure of 0.016 MPa and then allowed to stand for 1 hour in an environment at a temperature of 25° C., the ratio of the total area of the island portions of the sea-island structure is 28.0% or more and 35.0% or less, In the cross-sectional image, the circularity of the island portion is greater than or equal to 0.
75.
4. The adhesive film for metal terminals according to claim 1 or 3, characterized in that: In the cross-sectional image, the average grain size of the island portion is 0.3 μm or more.
5. The adhesive film for a metal terminal according to any one of claims 1 to 3, wherein: In the cross-sectional image, the circularity of the island portion is greater than or equal to 0.
75.
6. The adhesive film for metal terminal according to any one of claims 1 to 3, characterized in that: The thickness of the first polyolefin layer is 60 μm or less.
7. The adhesive film for metal terminal according to any one of claims 1 to 3, characterized in that: The thickness of the substrate is 60 μm or less.
8. The adhesive film for a metal terminal according to any one of claims 1 to 3, wherein: The second polyolefin layer has a thickness of 60 μm or less.
9. The adhesive film for a metal terminal according to any one of claims 1 to 3, wherein: The adhesive film for metal terminals has a thickness of 180 μm or less.
10. The adhesive film for a metal terminal according to any one of claims 1 to 3, wherein: The first polyolefin layer comprises a pigment.
11. The adhesive film for a metal terminal according to any one of claims 1 to 3, wherein: The substrate comprises a polyolefin backbone.
12. A method for producing an adhesive film for a metal terminal, wherein the adhesive film for a metal terminal is present between a metal terminal electrically connected to an electrode of an electric storage device element and an outer packaging material for an electric storage device that seals the electric storage device element, the method comprising: The adhesive film for metal terminals is composed of a laminated body, which has a first polyolefin layer arranged on the metal terminal side, a substrate, and a second polyolefin layer arranged on the outer packaging material side of the power storage device in this order. The ratio of the thickness of the substrate to the total thickness of the first polyolefin layer and the second polyolefin layer is 0.3 or more and 0.8 or less, The manufacturing method includes the step of obtaining a laminate having the first polyolefin layer, the substrate, and the second polyolefin layer in this order, In a cross-sectional image of the first polyolefin layer taken in a direction parallel to TD and in the thickness direction using a field emission scanning electron microscope, a sea-island structure was observed. The cross-sectional image is a cross-sectional image obtained in a range from the surface on the opposite side to the surface on the substrate side to a portion having a thickness of 30% when the thickness of the first polyolefin layer is taken as 100%. In the cross-sectional image after the adhesive film for metal terminals is allowed to stand for 12 seconds in a heating and pressurizing environment at a temperature of 190° C. and a surface pressure of 0.016 MPa and then allowed to stand for 1 hour in an environment at a temperature of 25° C., the ratio of the total area of the island portions of the sea-island structure is 28.0% or more and 35.0% or less, In the cross-sectional image, the particle size deviation of the island portion is 0.3 or less.
13. A metal terminal with an adhesive film for a metal terminal, characterized in that: The adhesive film for a metal terminal according to any one of claims 1 to 11 is disposed on a metal terminal.
14. An electric storage device, comprising an electric storage device element having at least a positive electrode, a negative electrode and an electrolyte, an outer packaging material for an electric storage device that encapsulates the electric storage device element, and metal terminals that are electrically connected to the positive electrode and the negative electrode, respectively, and extend to the outside of the outer packaging material for the electric storage device, wherein: The adhesive film for metal terminals according to any one of claims 1 to 11 is present between the metal terminal and the outer packaging material for an electric storage device.
15. A method for manufacturing an electric storage device, the electric storage device comprising an electric storage device element having at least a positive electrode, a negative electrode and an electrolyte, an outer packaging material for an electric storage device that encapsulates the electric storage device element, and metal terminals that are electrically connected to the positive electrode and the negative electrode, respectively, and extend to the outside of the outer packaging material for the electric storage device, the manufacturing method being characterized by: The method comprises the steps of allowing the adhesive film for metal terminal according to any one of claims 1 to 11 to be interposed between the metal terminal and the outer packaging material for the electric storage device, and sealing the electric storage device element with the outer packaging material for the electric storage device.
Citation Information
Patent Citations
Terminal with adhesive tape, method of manufacturing terminal with adhesive tape, and thin battery
JP2015079638A
